Adhesive composition and adhesive sheet

CN116867871BActive Publication Date: 2026-10-13NITTO DENKO CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202280014524.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-02-26
Filing Date
2022-01-21
Publication Date
2026-10-13
Estimated Expiration
2042-01-21

AI Technical Summary

Benefits of technology

[0012]但是,聚酯类聚合物通常仅在聚合物链的末端具有交联点,因此与丙烯酸类聚合物相比,不易得到有效的交联结构。因此,在聚酯类粘合剂中,提高剪切胶粘力并不容易。如果能实现具有高剪切胶粘力的聚酯类粘合剂,就可以提供在降低对化石资源类材料的依赖度的同时即使在胶粘面积小的情况下也不发生剥离的胶粘可靠性高的胶粘固定方法,这是有意义的。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116867871B_ABST
    Figure CN116867871B_ABST
Patent Text Reader

Abstract

The present invention provides an adhesive composition, in an adhesive containing a polyester-based polymer synthesized using a biomass material, in order to obtain high shear adhesive force, the adhesive composition contains a polyester-based polymer in which 50% or more of carbon constituting the polyester-based polymer is carbon from a biomass. The adhesive composition further contains a tackifying resin and a crosslinking agent. Furthermore, the polyester-based polymer contains an aromatic ring, the tackifying resin also contains an aromatic ring, and the crosslinking agent does not contain an aromatic ring.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an adhesive composition and an adhesive sheet.

[0002] This application claims priority to Japanese Patent Application No. 2021-030200, filed on February 26, 2021, the entire contents of which are incorporated herein by reference. Background Technology

[0003] Typically, adhesives (also known as pressure-sensitive adhesives, hereinafter the same) are soft solids (viscoelastics) in a temperature range near room temperature, possessing the property of easily adhering to the substrate under pressure. Utilizing this property, adhesives are typically used in the form of adhesive sheets comprising the adhesive layer, and are widely employed in various industries, from household appliances to automobiles, various machinery, electrical equipment, and electronic equipment, as a means of bonding that offers good operability and high adhesive reliability. Various adhesives, such as acrylic adhesives, rubber adhesives, and polyester adhesives, are used depending on the intended use, application location, and required properties. For example, patent documents 1-3 can be cited as prior art disclosures related to polyester adhesives.

[0004] Existing technical documents

[0005] Patent documents

[0006] Patent Document 1: Japanese Patent No. 4914132

[0007] Patent Document 2: Japanese Patent No. 6687997

[0008] Patent Document 3: Japanese Patent Application Publication No. 2020-79372 Summary of the Invention

[0009] The problem that the invention aims to solve

[0010] Adhesive sheets are preferably used for securing components in portable electronic devices such as mobile phones, smartphones, and tablets. Due to size and weight limitations, the adhesive area for securing components within portable electronic devices is typically small. Therefore, adhesive sheets used for this purpose need to have adhesive reliability that enables good fixation even over small areas, and the required performance is further enhanced by the demands for lightweighting and miniaturization. Particularly for portable electronic devices with touch panel displays, such as smartphones, the trend towards smaller and thinner products, coupled with larger screens for improved visual visibility and operability, necessitates adhesives used in these applications to maintain high adhesive reliability even under more demanding conditions. The ease of delamination can be evaluated, for example, by shear adhesive force. Shear adhesive force, unlike holding force, evaluates resistance to dynamic loads (i.e., shear forces) that could cause the adhesive interface to deviate. Adhesives with high shear adhesive force, for example, in securing components within portable electronic devices, exhibit high resistance to loads in shear directions that easily lead to delamination, effectively preventing peeling.

[0011] Incidentally, in recent years, environmental issues such as global warming have received increasing attention, with a desire to reduce the use of fossil fuels such as petroleum. This desire also extends to adhesive sheets used in portable electronic devices. Currently, acrylic adhesives, based on acrylic polymers, are the mainstream choice for adhesive sheets in portable electronic devices. Alternatively, synthetic rubber adhesives, based on rubber block copolymers such as styrene-butadiene block copolymers, can also be used. However, both acrylic and synthetic rubber adhesives rely primarily on fossil fuels such as petroleum, making it difficult to reduce fossil fuel consumption and limiting the transition to renewable organic resources. Polyester adhesives are considered to offer adhesive properties comparable to or better than those of acrylic and synthetic rubber adhesives, reducing reliance on fossil fuels. Polyester polymers used in polyester adhesives can be synthesized from biomass materials (e.g., Patent Documents 1 and 2), thus reducing the use of petroleum-based materials. Furthermore, polyester adhesives possess excellent chemical resistance, water resistance, durability, and optical properties (transparency), making them suitable for a wide range of applications, including portable electronic devices. It should be noted that biomass materials typically refer to materials derived from biological resources (typically photosynthetic plants) that can continuously reproduce in the presence of sunlight, water, and carbon dioxide.

[0012] However, polyester polymers typically have crosslinking points only at the ends of their polymer chains, making it more difficult to achieve effective crosslinking structures compared to acrylic polymers. Therefore, increasing shear strength in polyester adhesives is not easy. It would be significant to develop polyester adhesives with high shear strength, providing a reliable adhesive fixing method that reduces reliance on fossil-based materials while preventing delamination even with small adhesive areas.

[0013] The present invention has been made in view of the above circumstances, and its object is to provide an adhesive composition capable of exhibiting high shear adhesive strength in a composition comprising a polyester polymer synthesized using biomass materials. A related object is to provide an adhesive sheet having an adhesive layer comprising a polyester polymer synthesized using biomass materials.

[0014] means for solving problems

[0015] According to this specification, an adhesive composition is provided comprising a polyester polymer in which at least 50% of the constituent carbon is derived from biomass. The adhesive composition also comprises a tackifying resin and a crosslinking agent. Furthermore, the polyester polymer and the tackifying resin both contain aromatic rings, while the crosslinking agent does not contain aromatic rings. The above-described adhesive composition is prepared using a polyester polymer in which at least 50% of the constituent carbon is derived from biomass (biomass content is 50% or more), thus reducing dependence on fossil-based materials. Additionally, since both the polyester polymer and the tackifying resin in the above-described adhesive composition are aromatic-ringed substances, and a crosslinking agent without aromatic rings is used as the crosslinking agent, shear adhesion can be improved. Furthermore, the adhesive composition with the above composition readily exhibits good resilience.

[0016] In some preferred embodiments of the techniques disclosed herein (including adhesive compositions and adhesive sheets, hereinafter the same), the polyester polymer has a weight-average molecular weight of 30,000 or more. By using a polyester polymer with a weight-average molecular weight (Mw) of 30,000 or more, shear strength and resilience can be preferably improved. Furthermore, the use of polyester polymers with a specified Mw value or higher is also preferred in terms of improving high-temperature holding power.

[0017] In some preferred embodiments, the polyester polymer has a weight-average molecular weight greater than 100,000. By using polyester polymers with the above-mentioned Mw, superior shear adhesion and resilience can be achieved.

[0018] In some preferred embodiments, the aromatic ring ratio of the tackifying resin is 20% by weight or more. By using a tackifying resin with an aromatic ring ratio of 20% or more, it is easier to obtain higher shear strength and better resilience.

[0019] In some embodiments, the tackifying resin comprises a terpene phenol resin. When using a terpene phenol resin as the tackifying resin, the effects of the technology disclosed herein can preferably be achieved.

[0020] In some preferred embodiments, isocyanate-based crosslinking agents are preferably used as the crosslinking agents. Among these, aliphatic isocyanate compounds are particularly preferred. By using aliphatic isocyanate compounds as crosslinking agents, the degree of crosslinking can be effectively improved.

[0021] Furthermore, according to this specification, an adhesive sheet is provided having an adhesive layer comprising a polyester polymer, wherein more than 50% of the constituent carbon in the polyester polymer is derived from biomass. In this adhesive sheet, the adhesive layer further comprises a tackifying resin and a crosslinking agent. Moreover, the polyester polymer contains aromatic rings, the tackifying resin also contains aromatic rings, and the crosslinking agent does not contain aromatic rings. The adhesive sheet constructed as described above uses a polyester polymer with a biomass content of more than 50% in the adhesive, thus reducing dependence on fossil-based materials. Furthermore, since both the polyester polymer and the tackifying resin contain aromatic rings, and by employing a crosslinking agent without aromatic rings as the crosslinking agent composition, high shear adhesive strength can be obtained. Additionally, good resilience is readily obtained according to the above configuration.

[0022] In some preferred embodiments, the shear adhesion of the adhesive sheet to the stainless steel sheet is greater than 100 N / 100 mm. 2 Adhesive sheets with the aforementioned shear adhesive force can maintain high adhesive reliability, even in joints with small adhesive areas, and are not prone to peeling.

[0023] The adhesive sheet disclosed herein exhibits high shear strength and excellent adhesive reliability, making it suitable for applications in portable electronic devices requiring high-performance bonding and fastening. The use of adhesive sheets with high shear strength is particularly meaningful in portable electronic devices where the adhesive area is limited.

[0024] Furthermore, in recent years, displays with curved shapes, such as three-dimensional shapes, have become practical as displays used in electronic devices such as smartphones and OLED displays. It is desirable that the adhesives used in these applications possess durability against bending, and that even if the component adhered to the curved surface of the display has high elasticity, it exhibits adhesive reliability that resists the rebound force that would cause the component to return to its original shape without bulging or peeling. The adhesive sheet disclosed herein has good resilience, and therefore tends to have excellent adhesive reliability against bending, making it particularly preferable for applications such as adhesion to surfaces with curved shapes, such as three-dimensional shapes, found in portable electronic devices.

[0025] Furthermore, portable electronic devices contain heat-generating components such as batteries within a confined internal space. During prolonged use, the internal temperature rises due to the heat generated by these components. The repeated cycles of high and normal temperatures within the portable electronic device cause internal shrinkage of the adhered materials. Therefore, it is desirable to use an adhesive with holding power that does not slip under such shrinkage. As mentioned above, polyester polymers are generally less likely to achieve an effective cross-linking structure compared to acrylic polymers. For example, if the amount of cross-linking agent is increased to improve the degree of cross-linking in order to improve holding power, there is a concern that the gel fraction increases, resulting in decreased flexibility, adhesive strength, and impact resistance. Therefore, it is difficult to improve high-temperature holding power using the degree of cross-linking in polyester adhesives. However, the preferred adhesive sheet disclosed herein has a structure containing an adhesive layer of polyester polymer and exhibits excellent high-temperature holding power, making it suitable for fixing components within portable electronic devices from this perspective.

[0026] As described above, according to this specification, a portable electronic device using any of the adhesive sheets disclosed herein is provided; in other words, a portable electronic device incorporating such an adhesive sheet is provided. Attached Figure Description

[0027] Figure 1 A cross-sectional view illustrating the structure of an adhesive sheet according to one embodiment.

[0028] Figure 2 A cross-sectional view schematically illustrating the structure of an adhesive sheet according to another embodiment.

[0029] Figure 3 A cross-sectional view schematically illustrating the structure of an adhesive sheet according to another embodiment.

[0030] Figure 4 A front view schematically illustrating an example of a portable electronic device comprising an adhesive sheet.

[0031] Figure 5 A schematic diagram illustrating the method of the rebound test. Detailed Implementation

[0032] The preferred embodiments of the present invention will now be described. Matters necessary for carrying out the present invention, other than those specifically mentioned in this specification, will be understood by those skilled in the art based on the teachings for carrying out the invention as set forth in this specification and common technical knowledge at the time of application. The present invention can be implemented based on the disclosures in this specification and common technical knowledge in the field.

[0033] It should be noted that in the following figures, components / parts that perform the same function are sometimes labeled with the same reference numerals, and repeated descriptions may be omitted or simplified. Furthermore, for the purpose of clearly illustrating the invention, the embodiments described in the figures are schematic and do not necessarily accurately represent the dimensions or scale of the adhesive sheet of the invention actually provided as a product.

[0034] The adhesive sheet disclosed herein is composed of an adhesive layer. For example, the adhesive sheet may be a substrate-free double-sided adhesive sheet having a first adhesive surface formed by one surface of the adhesive layer and a second adhesive surface formed by the other surface of the adhesive layer. Alternatively, the adhesive sheet disclosed herein may also be a substrate-supported adhesive sheet obtained by laminating the adhesive layer on one or both sides of a supporting substrate. Hereinafter, the supporting substrate will sometimes be simply referred to as the "substrate".

[0035] <Example of adhesive sheet composition>

[0036] The structure of an adhesive sheet according to one embodiment is schematically shown. Figure 1 The adhesive sheet 1 is a substrate-free double-sided adhesive sheet consisting of an adhesive layer 21. The adhesive sheet 1 is used to adhere a first adhesive surface 21A (first surface) of the adhesive layer 21 and a second adhesive surface 21B (second surface) of the adhesive layer 21 to different parts of the object to be bonded. The adhesive surfaces 21A and 21B can be bonded to different parts of different components or different parts within a single component. Before use (i.e., before being bonded to the object), the adhesive sheet 1 is as follows: Figure 1As shown, the adhesive sheet 100 with release liner can be a structure in which the first adhesive surface 21A and the second adhesive surface 21B are protected by release liner 31, 32, with at least one side opposite to the adhesive layer 21 being the release surface. As the release liner 31, 32, for example, it is preferable to use a release liner formed by providing a release layer of release agent on one side of a sheet-like substrate (liner substrate), so that one side becomes the release surface. Alternatively, the release liner 32 can be omitted, and a release liner 31 with release surfaces on both sides can be used, overlapping it with the adhesive sheet 1 and wound into a spiral shape, thereby forming an adhesive sheet with release liner (roll-shaped) in which the second adhesive surface 21B is protected by contact with the back of the release liner 31.

[0037] The structure of the adhesive sheet according to another embodiment is schematically shown in Figure 2 The adhesive sheet 2 is configured as a single-sided adhesive sheet with a substrate, comprising: a sheet-like support substrate (e.g., a resin film) 10 having a first side 10A and a second side 10B, and an adhesive layer 21 disposed on the first side 10A. The adhesive layer 21 is fixedly disposed on the first side 10A of the support substrate 10, i.e., disposed on the first side 10A of the support substrate 10 in such a manner that there is no intention to separate the adhesive layer 21 from the support substrate 10. The adhesive sheet 2 before use is as follows: Figure 2 As shown, the adhesive sheet 200 with a release liner can be a component in which the surface (adhesive surface) 21A of the adhesive layer 21 is protected by a release liner 31, at least on the side opposite to the adhesive layer 21, which is the release surface. Alternatively, the release liner 31 can be omitted, and a support substrate 10 with the second surface 10B as the release surface can be used. By winding the adhesive sheet 2, the adhesive surface 21A is protected by contacting the second surface (back surface) 10B of the support substrate 10.

[0038] The structure of the adhesive sheet according to another embodiment is schematically shown in Figure 3 The adhesive sheet 3 is constructed as a double-sided adhesive sheet with a substrate, comprising: a sheet-like support substrate (e.g., a resin film) 10 having a first side 10A and a second side 10B; a first adhesive layer 21 fixedly disposed on the first side 10A; and a second adhesive layer 22 fixedly disposed on the second side 10B. The adhesive sheet 3 before use is as follows: Figure 3As shown, the adhesive sheet 300 with release liner can be a structure in which the surface (first adhesive surface) 21A of the first adhesive layer 21 and the surface (second adhesive surface) 22A of the second adhesive layer 22 are protected by release liner 31, 32. Alternatively, the release liner 32 can be omitted, and the release liner 31 with both sides as release surfaces can be used, overlapping it with the adhesive sheet 3 and wound into a spiral shape, thereby forming an adhesive sheet with release liner in a form where the second adhesive surface 22A is in contact with the back of the release liner 31 and is protected (rolled shape).

[0039] As the aforementioned release liner, release liners with a release treatment layer on the surface of the liner substrate such as resin film or paper, or release liners containing low-adhesion materials such as polyolefin resins (e.g., polyethylene, polypropylene) or fluorinated resins can be used. The release treatment layer can be formed, for example, by surface treatment of the liner substrate with release agents such as silicone, long-chain alkyl, fluorinated, or molybdenum sulfide. In the field of electronic devices, from the viewpoint of avoiding paper dust generation, release liners with a release treatment layer on the surface of the resin film or release liners containing low-adhesion materials are preferred.

[0040] It should be noted that the concept of adhesive sheet here can include items such as adhesive tape, adhesive film, and adhesive label. Adhesive sheet can be in roll form, single sheet form, or it can be obtained by cutting, punching, etc., depending on its purpose or usage.

[0041] <Adhesive layer>

[0042] (Polyester polymers)

[0043] The adhesive sheet disclosed herein has an adhesive layer comprising a polyester polymer. In other words, the aforementioned adhesive layer and the adhesive composition used to form the adhesive layer comprise a polyester polymer (hereinafter, unless otherwise specified, the description of the adhesive layer also applies to the adhesive composition). Adhesives and adhesive compositions comprising polyester polymers in this way are referred to as polyester adhesives and polyester adhesive compositions. The aforementioned polyester polymer is typically included as a base polymer in the adhesive layer. Here, the base polymer refers to the main component of the rubbery polymer (a polymer exhibiting rubber elasticity in a temperature range near room temperature) contained in the adhesive layer. Furthermore, unless otherwise specified, "main component" in this specification refers to a component with a content greater than 50% by weight. Additionally, in this specification, a polyester polymer refers to a polymer obtained by polycondensation of a dicarboxylic acid and a diol.

[0044] The polyester polymer contained in the adhesive layer contains at least 50% of the carbon components derived from biomass. In other words, the biomass carbon ratio (also known as biomass percentage) of the aforementioned polyester polymer is 50% or more. By using polyester polymers with a biomass percentage of a specified value or higher, the dependence of the adhesive on fossil-based materials can be reduced. In some embodiments, a biomass percentage of 52% or more, or 55% or more, is appropriate, and for example, it can be 60% or more. The biomass percentage of the polyester polymer is preferably 70% or more, more preferably 75% or more, further preferably 80% or more, and can be 85% or more, or 88% or more. The upper limit of the biomass percentage is defined as 100%, but in some embodiments, the biomass percentage of the polyester polymer can be, for example, 95% or less. In cases where adhesive performance is of greater importance, the biomass percentage can be 92% or less, 90% or less, or 85% or less. By using compounds derived from biomass in at least one (e.g., both) of the dicarboxylic acids and diols used in the synthesis of polyester polymers, it is possible to achieve a biomass content of over 50% in the polyester polymers.

[0045] In this specification, carbon derived from biomass refers to carbon derived from biomass materials, i.e., carbon derived from renewable organic resources (renewable carbon). The aforementioned biomass materials typically refer to materials derived from biological resources (typically photosynthetic plants) that can continuously reproduce as long as sunlight, water, and carbon dioxide are present. Therefore, materials derived from fossil resources depleted through extraction and subsequent use (fossil resources) are excluded from the concept of biomass materials herein. The biomass percentage of polyester polymers, i.e., the proportion of carbon derived from biomass in the total carbon content of the polyester polymer, can be estimated by the carbon isotope content of mass number 14 as determined according to ASTM D6866. The same applies to the examples described later.

[0046] The polyester polymers used in the technology disclosed herein have aromatic rings within their polymer molecules. By using the polyester polymer containing aromatic rings with a tackifying resin containing aromatic rings, shear adhesion can be improved. It is believed that by including aromatic rings in the polyester polymer, the adhesive possesses moderate hardness (elasticity), while simultaneously increasing the interaction (π-π stacking) between the polyester polymer and the aromatic rings contained in the tackifying resin, thereby improving cohesion and contributing to improved shear adhesion. It should be noted that the technology disclosed herein is not limited to the above explanation. Furthermore, by using polyester polymers containing aromatic rings, good resilience and high-temperature retention are readily obtained. The aforementioned aromatic rings are introduced into the polymer using monomers containing aromatic rings (aromatic dicarboxylic acids, aromatic diols). In polyester polymers containing aromatic rings, the copolymerization ratio of aromatic ring-containing monomers (typically aromatic dicarboxylic acids or aromatic diols) is not particularly limited, but is preferably about 1% by weight or more. From the viewpoint of improving shear adhesion, the copolymerization ratio of aromatic ring-containing monomers is preferably about 3% by weight or more, more preferably about 5% by weight or more, and even more preferably about 7% by weight or more. There is a tendency that the higher the copolymerization ratio of aromatic ring-containing monomers, the better the high-temperature retention strength. In addition, the upper limit of the above-mentioned copolymerization ratio of aromatic ring-containing monomers is, for example, about 30% by weight or less. From the viewpoint of adhesive properties such as adhesive strength, it is preferably about 15% by weight or less, more preferably about 12% by weight or less, even more preferably about 10% by weight or less, and particularly preferably about 8% by weight or less.

[0047] Furthermore, the weight-average molecular weight (Mw) of the polyester polymer is not particularly limited, but is generally about 10,000 or more, for example, about 20,000 or more is suitable. In some embodiments, the Mw of the polyester polymer is 30,000 or more, and greater than 50,000 is suitable. From the viewpoint of obtaining superior properties, it is preferable to have a Mw greater than 60,000, more preferably greater than 70,000, further preferably greater than 80,000, particularly preferably greater than 90,000, and can be 95,000 or more. By using polyester polymers with a Mw of a specified value or higher, the cohesiveness of the adhesive layer is improved, as are the shear strength and resilience. In addition, by using polyester polymers with high Mw, the holding power and thus the high-temperature holding power can be improved. In some preferred embodiments, the Mw of the polyester polymer is greater than 100,000, more preferably 110,000 or more (e.g., greater than 110,000), further preferably 120,000 or more, and can be 125,000 or more. By using such high molecular weight polyester polymers, superior shear adhesion and resilience can be easily obtained. The upper limit of the molecular weight (Mw) of polyester polymers is typically about 30 × 10⁻⁶. 4 The following is appropriate, and from the viewpoint of adhesive strength, it is preferably about 20 × 10. 4Hereinafter, approximately 15×10 is preferred. 4 For example, it could be approximately 12 × 10 4 the following.

[0048] It should be noted that in this specification, the Mw of polyester polymers refers to the value converted from standard polystyrene obtained by GPC (gel permeation chromatography). For example, a GPC apparatus named "HLC-8320GPC" (column: TSKgelGMH-H(S), manufactured by Tosoh Corporation) can be used. More specifically, GPC determinations can be performed under the following conditions. The determinations were also performed using the same method in the examples described later.

[0049] [GPC Measurement]

[0050] Column: TSKgelGMH-H(S)

[0051] Column temperature: 40℃

[0052] Eluent: THF (with added amine components 0.1% by weight)

[0053] Flow rate: 0.5 mL / min

[0054] Injection volume: 100μL

[0055] Detector: Differential refractometer (RI)

[0056] Standard sample: Polystyrene (PS)

[0057] It is advantageous for polyester polymers to have a glass transition temperature (Tg) of about 15°C or less, preferably about 0°C or less, more preferably about -15°C or less, even more preferably about -20°C or less, and particularly preferably about -25°C or less (e.g., about -30°C or less). By using polyester polymers with low Tg, adhesive strength can be preferably improved. Furthermore, from the viewpoint of the cohesiveness of the adhesive layer, the Tg of polyester polymers is typically about -80°C or more, preferably about -60°C or more, more preferably about -45°C or more, even more preferably about -40°C or more, and can be about -35°C or more. The Tg of polyester polymers can be adjusted by appropriately changing the monomer composition (i.e., the type or ratio of monomers used in the synthesis of the polymer).

[0058] The glass transition temperature (Tg) of polyester polymers was determined using the following method: A disc-shaped test piece, 2 mm thick and 8 mm in diameter, was prepared using the polyester polymer to be tested. This test piece was sandwiched between parallel plates used for shear testing, and the peak value of tanδ (loss modulus G” / storage modulus G’) was determined at a frequency of 1 Hz using a measuring device (ARES, manufactured by Rheometric Scientific). The temperature of this peak value was set as Tg (glass transition temperature) [°C]. The same method was used to determine the Tg in the examples described later.

[0059] (Dicarboxylic acid)

[0060] The dicarboxylic acid used in the synthesis of the aforementioned polyester polymers can be any of the following: aliphatic dicarboxylic acids, dimer acids, alicyclic dicarboxylic acids, unsaturated dicarboxylic acids, and aromatic dicarboxylic acids. Specific examples of dicarboxylic acids include: aliphatic dicarboxylic acids such as malonic acid, succinic acid, glutaric acid, dimethylglutaric acid, adipic acid, trimethyl adipic acid, pimelic acid, octanoic acid, azelaic acid, dodecanoic acid, sebacic acid, thiodipropionic acid, and diglycolic acid; dimer acids obtained by dimerizing fatty acids such as oleic acid and erucic acid; and 1,2-cyclopentanedicarboxylic acid, 1,2-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, and 1,4-cyclohexanedicarboxylic acid. Alicyclic dicarboxylic acids such as 4-methyl-1,2-cyclohexanedicarboxylic acid, norbornenedicarboxylic acid, and adamantanedicarboxylic acid; unsaturated dicarboxylic acids such as maleic acid, maleic anhydride, fumaric acid, itaconic acid, citraconic acid, and dodecenylsuccinic anhydride; aromatic dicarboxylic acids such as isophthalic acid, terephthalic acid, phthalic acid, benzylmalonic acid, 2,2'-biphenyl dicarboxylic acid, 4,4'-biphenyl dicarboxylic acid, 4,4'-dicarboxylic acid diphenyl ether, and naphthalenedicarboxylic acid; and their derivatives. It should be noted that the derivatives of the above dicarboxylic acids include carboxylates, carboxylic anhydrides, carboxylic halides, and carboxylic esters. By appropriately selecting one or more of these dicarboxylic acids, polyester polymers that exhibit the desired properties (specifically, high shear strength, preferably further enhanced resilience, high-temperature retention, etc.) can be obtained.

[0061] From the viewpoint of obtaining polyester polymers with a biomass content of 50% or more, plant-derived dicarboxylic acids are preferred as dicarboxylic acids. Preferred examples of such dicarboxylic acids include: sebacic acid derived from plants (e.g., castor oil); and dimer acids derived from fatty acids such as oleic acid and erucic acid. Plant-derived dicarboxylic acids can be used alone or in combination of two or more.

[0062] From the viewpoint of reducing dependence on petroleum-based materials, it is appropriate for the weight percentage of plant-derived dicarboxylic acids in the total amount (total weight) of dicarboxylic acids used as monomer components in polyester polymers to be about 1% by weight or more, preferably about 10% by weight or more, more preferably about 50% by weight or more, further preferably about 70% by weight or more, particularly preferably about 80% by weight or more, and may also be about 90% by weight or more, or about 95% by weight or more (e.g., 95% to 100% by weight). Furthermore, the upper limit of the aforementioned weight percentage of plant-derived dicarboxylic acids is 100% by weight. From the viewpoint of adhesive properties, it is appropriate for the weight percentage of plant-derived dicarboxylic acids to be about 99% by weight or less, preferably about 95% by weight or less, and may also be about 90% by weight or less.

[0063] In some preferred embodiments, dimer acid is used as a dicarboxylic acid derived from plants. By using dimer acid, it is possible to improve the biomass yield of polyester polymers while obtaining good adhesive properties. Dimer acid can be used alone or in combination of two or more. In the method of using dimer acid as the aforementioned dicarboxylic acid, it is appropriate for the weight percentage of dimer acid in the total amount (total weight) of dicarboxylic acids that are monomer components of the polyester polymer to be about 1% by weight or more, preferably about 10% by weight or more, more preferably about 50% by weight or more, further preferably about 70% by weight or more, particularly preferably about 80% by weight or more, and may also be about 90% by weight or more, and may be about 95% by weight or more (e.g., 95% to 100% by weight). By using a predetermined amount or more of dimer acid, polymers can be designed based on the properties of dimer acid. Furthermore, the upper limit of the weight percentage of the aforementioned dimer acid is 100% by weight. From the viewpoint of adhesive properties such as shear strength, resilience, and high-temperature retention, it is appropriate for the weight percentage of the aforementioned dimer acid to be about 99% by weight or less, preferably about 95% by weight or less, and also about 90% by weight or less.

[0064] In some methods, sebacic acid can be used as a dicarboxylic acid derived from plants. Using sebacic acid can improve the biomass yield of polyester polymers. In methods using sebacic acid as the aforementioned dicarboxylic acid, the weight percentage of sebacic acid in the total amount (total weight) of the dicarboxylic acids used as monomer components of the polyester polymer can be about 1% by weight or more, for example, about 10% by weight or more, about 50% by weight or more, about 70% by weight or more, or about 90% by weight or more (e.g., 95% to 100% by weight). Alternatively, the aforementioned weight percentage of sebacic acid can be about 95% by weight or less; from the viewpoint of adhesive properties, the aforementioned weight percentage of sebacic acid can be about 75% by weight or less, or about 60% by weight or less. The technology disclosed herein can also be implemented in either a manner where the dicarboxylic acid used as a monomer component in the synthesis of the polyester polymer includes sebacic acid or a manner where the dicarboxylic acid used as a monomer component in the synthesis of the polyester polymer does not contain sebacic acid. For example, the weight percentage of sebacic acid can be less than about 50% by weight, less than about 30% by weight, less than about 10% by weight, less than about 3% by weight, or less than 1% by weight. The dicarboxylic acid used in the synthesis of polyester polymers can also be substantially free of sebacic acid.

[0065] There are no particular limitations on the molecular weight of the plant-derived dicarboxylic acids mentioned above; 100 or more is appropriate, and 150 or more is possible. The higher the molecular weight of the plant-derived dicarboxylic acids, the easier it is to improve the biomass yield of polyester polymers. From this perspective, the molecular weight of plant-derived dicarboxylic acids can be 250 or more, 350 or more, 450 or more, or even 500 or more (e.g., 550 or more). On the other hand, from the perspective of monomer availability and synthetic feasibility, a molecular weight of approximately 1000 or less is appropriate for plant-derived dicarboxylic acids; for example, it can be 800 or less, 700 or less, or even 600 or less. As a preferred example of a dicarboxylic acid with the above molecular weight, dimer acids can be cited.

[0066] It should be noted that, in this specification, the molecular weight of dicarboxylic acids is the molecular weight calculated from the chemical formula. Furthermore, when using two or more dicarboxylic acids (such as the plant-derived dicarboxylic acids mentioned above), the molecular weight of the dicarboxylic acid (such as the plant-derived dicarboxylic acids mentioned above) is the sum of the products of the molecular weight and weight fraction of each dicarboxylic acid (total value).

[0067] Furthermore, aromatic dicarboxylic acids are preferred as the dicarboxylic acids used in the synthesis of the polyester polymers disclosed herein. By using dicarboxylic acids containing aromatic dicarboxylic acids, there is a tendency to improve cohesive strength and shear adhesive strength. The use of aromatic dicarboxylic acids is advantageous from the viewpoint of improving resilience and high-temperature retention. By including aromatic dicarboxylic acids as the dicarboxylic acid, the amount of crosslinking agent used can be controlled, thus easily improving cohesive strength while maintaining or improving adhesive strength. Preferred examples of aromatic dicarboxylic acids include isophthalic acid, terephthalic acid, and phthalic acid, with terephthalic acid being more preferred. These can be used alone or in combination of two or more.

[0068] It should be noted that the technology disclosed herein includes methods for improving the biomass yield of polyester polymers by using aromatic dicarboxylic acids derived from biomass. In some methods, terephthalic acid and its derivatives derived from biomass can be used as the aforementioned dicarboxylic acid. There are no particular limitations on the methods for obtaining the aforementioned dicarboxylic acids derived from biomass. For example, terephthalic acid derived from biomass can be obtained by the following method: isobutanol is obtained from corn, sugars, or wood, and then converted into isobutene; isobutene is dimerized to obtain isooctene; p-xylene is synthesized by the method described in Chemische Technik, Vol. 38, No. 3, pp. 116-119, 1986, i.e., through free radical cleavage, recombination, and cyclization; and then p-xylene is oxidized to obtain terephthalic acid (International Publication No. 2009 / 079213).

[0069] In the use of aromatic dicarboxylic acids as dicarboxylic acids, there is no particular limitation on the weight percentage of aromatic dicarboxylic acids in the total amount (total weight) of dicarboxylic acids in the monomer components of polyester polymers. A weight percentage of about 1% or more is suitable, and from the viewpoint of improving shear adhesion, a weight percentage of about 3% or more is preferred, more preferably about 5% or more, and even more preferably about 7% or more. Furthermore, the upper limit of the aforementioned weight percentage of aromatic dicarboxylic acids is not limited to a specific range, as it may vary depending on the type of dicarboxylic acid, etc. For example, a weight percentage of about 50% or less is suitable, and from the viewpoint of adhesive properties such as adhesive strength, a weight percentage of about 30% or less is preferred, more preferably about 20% or less, even more preferably about 15% or less, and particularly preferably about 10% or less.

[0070] In some approaches, considering productivity, efficiency, cost, and the desired adhesive properties, dicarboxylic acids (e.g., aliphatic dicarboxylic acids) derived from fossil resources may be used. Examples of such dicarboxylic acids (e.g., aliphatic dicarboxylic acids) include: dimethylglutaric acid, adipic acid, trimethyl adipic acid, pimelic acid, octanoic acid, and azelaic acid. Among these, adipic acid is preferred as an aliphatic dicarboxylic acid. The aforementioned dicarboxylic acids (e.g., aliphatic dicarboxylic acids) derived from fossil resources may be used alone or in combination of two or more.

[0071] The molecular weight of the dicarboxylic acid used as a monomer component in the synthesis of the polyester polymers disclosed herein is not particularly limited; 100 or more is suitable, and it can be 150 or more. In some embodiments, the molecular weight of the dicarboxylic acid used can be 200 or more, 250 or more, 350 or more, 450 or more, or even 500 or more (e.g., 530 or more). On the other hand, from the viewpoint of monomer availability and syntheticity, a molecular weight of about 1000 or less of the dicarboxylic acid is suitable; for example, it can be 800 or less, 700 or less, or even 600 or less (e.g., 550 or less). The polyester polymers disclosed herein (polyester polymers with a specified Mw value or higher, preferably with a specified Tg range) are preferably synthesized using dicarboxylic acids with molecular weights within the above-mentioned ranges.

[0072] (Diol)

[0073] The diol used in the synthesis of the polyester polymers disclosed herein may be any one of (poly)alkylene diols, aliphatic diols, dimerized diols, alicyclic diols, aromatic diols, or unsaturated diols. Specific examples of the aforementioned diols include: ethylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, propylene glycol, dipropylene glycol, polypropylene glycol, polytetramethylene glycol, and other (poly)alkylene diols; 1,3-propanediol, 2-methyl-1,3-propanediol, 2,2-dimethyl-1,3-propanediol (neopentyl glycol), 2-ethyl-2-butyl-1,3-propanediol, 2-ethyl-2-isobutyl-1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, 2-methyl-1,3-hexanediol, 2,2,4-trimethyl-1, Aliphatic diols such as 6-hexanediol, 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol; dimerized diols (dimerized diols derived from fatty acids such as oleic acid and erucic acid); alicyclic diols such as 1,2-cyclohexanediol, 1,3-cyclohexanediol, 1,4-cyclohexanediol, spirodiol, tricyclodecanediol, adamantanediol, and 2,2,4,4-tetramethyl-1,3-cyclobutanediol; aromatic diols such as 4,4'-thiodiphenol, 4,4'-methylenediphenol, 4,4'-dihydroxybiphenyl, catechol, resorcinol, hydroquinone, 2,5-naphthalenediol, p-xylenediol, and their ethylene oxide and propylene oxide adducts. By appropriately selecting one or more of these diols, polyester polymers that can exhibit the desired properties (specifically, high shear adhesion, preferably one or more of the following: resilience, high temperature retention, etc.) can be obtained.

[0074] In some methods, the preferred diols are (poly)alkylene diols, aliphatic diols, and alicyclic diols, with (poly)alkylene diols and aliphatic diols being more preferred. By combining these diols (preferably ethylene glycol and aliphatic diols) with the aforementioned dicarboxylic acids (preferably dimer acids and aromatic dicarboxylic acids), polyester polymers with excellent adhesive properties can be preferably obtained. Preferred examples include: (poly)ethylene glycol, 1,3-propanediol, 2-methyl-1,3-propanediol, 2,2-dimethyl-1,3-propanediol (neopentyl glycol), 1,4-butanediol, 1,5-pentanediol, and 1,6-hexanediol. From the viewpoint of reactivity, ethylene glycol, 1,3-propanediol, 2,2-dimethyl-1,3-propanediol, 1,4-butanediol, and 1,6-hexanediol are more preferred. These can be used alone or in combination of two or more. The aforementioned (poly)alkylene diols, aliphatic diols, and alicyclic diols can be derived from plants or from fossil resources. It should be noted that in this specification, the term (poly)ethylene glycol is used to encompass the meanings of ethylene glycol, diethylene glycol, triethylene glycol, and polyethylene glycol.

[0075] The weight percentage (preferably the weight percentage of ethylene glycol and aliphatic diols) of the total amount of diols in the monomer components of polyester polymers is not particularly limited, but is suitable to be about 50% by weight or more. From the viewpoint of obtaining good adhesive properties, it is preferable to be about 70% by weight or more, more preferably about 80% by weight or more, further preferably about 90% by weight or more, and particularly preferably about 95% by weight or more (e.g., 99% to 100% by weight). In addition, the weight percentage (preferably the weight percentage of ethylene glycol and aliphatic diols) of the above-mentioned (poly)alkylene diols, aliphatic diols, and aliphatic diols can be, for example, about 95% by weight or less.

[0076] In some preferred embodiments, polyethylene glycol (PEG) can be used as the diol. By combining PEG with a suitable dicarboxylic acid, good adhesive properties (shear adhesion, etc.) can preferably be obtained. When using PEG as the diol, it is appropriate for the weight percentage of PEG in the total amount (total weight) of the diols that are monomer components of the polyester polymer to be about 1% by weight or more, preferably about 10% by weight or more, more preferably about 50% by weight or more, further preferably about 80% by weight or more, and particularly preferably about 90% by weight or more (e.g., 95% to 100% by weight). By using an amount of PEG of a specified value or more, the polymer can be designed based on the properties of PEG. Furthermore, for example, by using PEG, an adhesive layer with low haze is easily obtained. Additionally, the weight percentage of PEG can be about 95% by weight or less, about 70% by weight or less, or about 50% by weight or less. The aforementioned polyethylene glycol can be derived from plants or fossil resources. Polyethylene glycol can be used alone or in combination of two or more.

[0077] In some approaches, plant-derived diols are preferred from the viewpoint of obtaining polyester polymers with a biomass content of 50% or more. Examples of such diols include: biomass diols obtained from bioethanol (e.g., biomass (poly) glycol), fatty acid esters derived from plants (e.g., castor oil), dimerized diols derived from fatty acids such as oleic acid and erucic acid, and butylene glycol produced using glucose. Plant-derived diols can be used alone or in combination of two or more.

[0078] In some approaches, from the viewpoint of reducing dependence on petroleum-based materials, the weight percentage of plant-derived diols in the total amount (total weight) of diols that are monomeric components of polyester polymers can be approximately 1% by weight or more, approximately 10% by weight or more, approximately 50% by weight or more, approximately 80% by weight or more, or approximately 90% by weight or more (e.g., 95% to 100% by weight). Alternatively, the aforementioned weight percentage of plant-derived diols can be approximately 95% by weight or less, approximately 70% by weight or less, or approximately 50% by weight or less. Even in approaches where the amount of plant-derived diols used is relatively low and petroleum-derived diols are used, for example, by using diols with relatively low molecular weights derived from petroleum, polyester polymers can achieve a biomass yield of a specified value or higher. From this viewpoint, the aforementioned weight percentage of plant-derived diols can be approximately 30% by weight or less, approximately 10% by weight or less, or approximately 3% by weight or less (e.g., less than 1% by weight). The technology disclosed herein can preferably be implemented in a manner in which the diols used as monomer components in the synthesis of polyester polymers are substantially free of plant-derived diols.

[0079] In some methods, dimerized glycols can be used as plant-derived diols. By using dimerized glycols, the biomass yield of polyester polymers can be increased. Dimerized glycols can be used alone or in combination of two or more. In methods using dimerized glycols as the aforementioned diols, the weight percentage of dimerized glycols in the total amount (total weight) of diols used as monomeric components of the polyester polymer can be about 1% by weight or more, for example, about 10% by weight or more, about 50% by weight or more, about 70% by weight or more, about 80% by weight or more, or about 90% by weight or more (e.g., 95% by weight to 100% by weight). Alternatively, the aforementioned weight percentage of dimerized glycols can be about 95% by weight or less, about 85% by weight or less, or about 60% by weight or less. The technology disclosed herein can be implemented in either a manner where the diols used as monomeric components in the synthesis of polyester polymers contain dimerized glycols or in a manner where the diols used as monomeric components in the synthesis of polyester polymers do not contain dimerized glycols. For example, the weight percentage of the aforementioned dimer glycol may be less than about 50% by weight (e.g., less than 50% by weight), less than about 30% by weight, less than about 10% by weight, less than about 3% by weight, or less than 1% by weight. The diol used in the synthesis of polyester polymers may substantially not contain dimer glycol.

[0080] There are no particular limitations on the molecular weight of the aforementioned diols. From the viewpoint of monomer availability and syntheticity, a molecular weight of 500 or less is suitable, for example, it can be 300 or less, 150 or less, 100 or less, or 80 or less. Furthermore, a molecular weight of approximately 50 or more is suitable, for example, it can be greater than 100. Using diols within the aforementioned molecular weight range allows for the preferred synthesis of polyester polymers exhibiting high shear adhesion. Additionally, for example, in the case where the diol is derived from fossil resources, a molecular weight of 500 or less from the fossil resource is suitable, for example, it can be 300 or less. The smaller the molecular weight of the diol from the fossil resource, the easier it is for the polyester polymer to have a high biomass yield. From this viewpoint, a molecular weight of 150 or less, 100 or less, or 80 or less from the fossil resource is suitable. Furthermore, a molecular weight of approximately 50 or more from the fossil resource is suitable, for example, it can be greater than 100. Ethylene glycol is a preferred example of a diol having the aforementioned molecular weight.

[0081] It should be noted that, in this specification, the molecular weight of a diol can be the molecular weight calculated from its chemical formula. Furthermore, when using two or more diols (such as the diols derived from fossil resources mentioned above), the molecular weight of the diol (such as the diols derived from fossil resources mentioned above) is the sum of the products of the molecular weight and weight fraction of each diol (total value).

[0082] The polyester polymers disclosed herein can essentially be composed of the aforementioned dicarboxylic acids and diols. However, to introduce desired functional groups, adjust molecular weight, etc., other copolymerizing components besides dicarboxylic acids and diols can be copolymerized without impairing the effects of the disclosed technology. Examples of such other copolymerizing components include: polycarboxylic acids containing three or four or more carboxyl groups (trimethylammonia, pyromellitic acid, adamantane tricarboxylic acid, pyromellitic acid, trimeric acids, etc., which are ternary or higher polycarboxylic acids); polyols containing three or four or more hydroxyl groups per molecule (pentaerythritol, dipentaerythritol, tripentaerythritol, glycerol, trimethylolpropane, trimethylolethane, 1,3,6-hexanetriol, adamantanetriol, etc.); monocarboxylic acids; monohydric alcohols; hydroxycarboxylic acids; lactones, etc. These other copolymerizing components can be used alone or in combination of two or more. These other copolymerizing components may or may not be derived from plants. The proportion of the aforementioned other copolymer components in the monomer composition of the polyester polymer is preferably less than 10% by weight, for example, less than 3% by weight, typically less than about 1% by weight (further less than about 0.1% by weight). The technique disclosed herein can preferably be implemented in a manner in which the monomer composition of the polyester polymer substantially does not contain the aforementioned other copolymer components.

[0083] There are no particular limitations on the monomer components used in the synthesis of the polyester polymers disclosed herein. A total ratio of about 90% by weight or more for dicarboxylic acids and diols is suitable, preferably about 95% by weight or more, more preferably about 98% by weight or more, and even more preferably about 99% by weight or more (e.g., 99% to 100% by weight). The technology disclosed herein is preferably implemented in a manner that substantially uses polyester polymers synthesized from dicarboxylic acids and diols.

[0084] In some preferred embodiments, the monomer components of the polyester polymer are combined using a dimer acid as a dicarboxylic acid and polyethylene glycol as a diol. By using the dimer acid and polyethylene glycol in combination, it is preferable to synthesize polyester polymers with a specified Mw value or higher and capable of exhibiting shear adhesive strength. It is appropriate for the total proportion of dimer acid and polyethylene glycol in the total monomer components of the polyester polymer to be about 50% by weight or more, preferably about 60% by weight or more, more preferably about 70% by weight or more, further preferably about 80% by weight or more, and may also be about 90% by weight or more (e.g., 99% to 100% by weight).

[0085] The method for obtaining polyester polymers disclosed herein is not particularly limited, and polymerization methods known as methods for synthesizing polyester polymers can be appropriately employed. The monomer raw materials used for synthesizing polyester polymers can be, for example, substances obtained by adding monomers in a manner where, relative to 1 equivalent of a diol, the dicarboxylic acid is 0.95 to 1.05 equivalents (preferably 0.98 to 1.02 equivalents). By adding dicarboxylic acid and diol in the above proportions, high molecular weight polyester polymers are readily obtained. Furthermore, the above polymers can be moderately crosslinked (e.g., crosslinking based on a reaction with crosslinking agents such as isocyanate crosslinking agents) to improve cohesiveness.

[0086] In the disclosed technology, the weight ratio of dicarboxylic acid to diol used as a monomer component in the synthesis of polyester polymers is not particularly limited, and an appropriate weight ratio can be set considering the physical properties and synthetic properties of the target polymer. In some embodiments, the weight ratio (weight ratio A1 / A2) of the dicarboxylic acid used as a monomer component (A1) can be 10 / 90 or more, or 30 / 70 or more. In some preferred embodiments, the weight ratio (A1 / A2) is about 50 / 50 or more, more preferably 60 / 40 or more, even more preferably 70 / 30 or more, or 80 / 20 or more, or 90 / 10 or more. For example, by increasing the weight ratio of dicarboxylic acid as described above, the properties based on dicarboxylic acid can be appropriately expressed. In addition, in the case of using dicarboxylic acid derived from plants, the biomass yield of the obtained polyester polymer can be effectively increased. Furthermore, the weight ratio (A1 / A2) can be, for example, 95 / 5 or less, or 85 / 15 or less. In some methods, from the viewpoint of appropriately representing the properties based on diols, the aforementioned weight ratio (A1 / A2) can be 75 / 25 or less, or even 50 / 50 or less (e.g., 30 / 70 or less). In methods using plant-derived diols, by setting the aforementioned weight ratio, polyester polymers can achieve high biomass yields. It should be noted that in methods where both the dicarboxylic acid and the diol are derived from plant materials, regardless of the weight ratio of the dicarboxylic acid to the diol, polyester polymers with biomass yields exceeding a specified value can be obtained.

[0087] The polyester polymers disclosed herein are similar to conventional polyesters and can be obtained by polycondensation of dicarboxylic acids and diols. More specifically, the reaction between the carboxyl group of the dicarboxylic acid and the hydroxyl group of the diol occurs simultaneously with the removal of water (product water) typically generated by the above reaction from the reaction system, thereby enabling the synthesis of polyester polymers. Methods for removing the product water from the reaction system include: injecting an inert gas into the reaction system to expel the product water along with the inert gas; azeotropic dehydration with toluene, xylene, or other solvents used to remove the product water; distilling the product water from the reaction system under reduced pressure (reduced pressure method); etc.

[0088] To effectively obtain polyester polymers with the desired properties (e.g., molecular weight), the reaction temperature, reaction time, and, in the case of a reduced pressure method, the pressure within the reaction system can be appropriately set during the above-mentioned reactions (including esterification and polycondensation). While there are no particular limitations, a reaction temperature of approximately 150°C or higher (e.g., 180°C to 260°C) is generally suitable. Maintaining the reaction temperature within this range allows for a good reaction rate, increased productivity, and easier prevention or suppression of degradation of the resulting polyester polymer. The reaction time is not particularly limited and can range from approximately 3 hours to approximately 48 hours (e.g., approximately 10 hours to approximately 30 hours). In the case of a reduced pressure method, there are no particular limitations, but a pressure of 10 kPa or lower (typically 10 kPa to 0.1 kPa) is generally suitable, for example, 4 kPa to 0.1 kPa. Maintaining the pressure within the reaction system within the above range allows for the effective distillation removal of water generated during the reaction, easily maintaining a good reaction rate. Furthermore, at relatively high reaction temperatures, maintaining the pressure within the reaction system above the aforementioned lower limit effectively prevents the dicarboxylic acids and diols used as raw materials from being distilled off the system. From the viewpoint of maintaining a stable pressure within the reaction system, a pressure of 0.1 kPa or higher is generally appropriate.

[0089] Similar to the synthesis of typical polyesters, the above reactions can utilize appropriate amounts of known or even conventional catalysts for esterification and condensation. Examples of such catalysts include various metal compounds containing titanium, germanium, antimony, tin, zinc, etc.; and strong acids such as p-toluenesulfonic acid and sulfuric acid. The amount of catalyst used can be appropriately determined based on the reaction rate, etc., therefore detailed descriptions are omitted here.

[0090] In the above-described process of synthesizing polyester polymers via the reaction of dicarboxylic acids and diols, a solvent may or may not be used. The synthesis can be carried out in a manner that substantially eliminates the use of organic solvents (meaning, for example, excluding the intentional use of organic solvents as reaction solvents in the above-described reactions). Therefore, synthesizing polyester polymers in a manner substantially eliminating the use of organic solvents, and preparing polyester adhesives using these polyester polymers, is preferable as it meets the requirements for controlling the use of organic solvents during their manufacturing process.

[0091] It should be noted that in the above reactions, there is usually a correlation between the molecular weight of the synthesized polyester polymer and the viscosity of the reaction system. Therefore, this can be used to control the molecular weight of the polyester polymer. For example, by continuously or intermittently measuring (monitoring) the torque of the stirrer and the viscosity of the reaction system during the reaction, polyester polymers that meet the target molecular weight can be synthesized with high precision.

[0092] (Tackifying resin)

[0093] The adhesive layer (and adhesive composition) disclosed herein comprises a tackifying resin. As the tackifying resin, a tackifying resin having an aromatic ring within its molecule (a tackifying resin containing an aromatic ring) can be used. By using a tackifying resin containing an aromatic ring in conjunction with a polyester polymer containing an aromatic ring, shear adhesion can be improved. Furthermore, by using a tackifying resin containing an aromatic ring, good resilience and high-temperature retention are readily obtained. Additionally, by having both the aforementioned polyester polymer and the tackifying resin possess aromatic rings, excellent compatibility is achieved, and the desired adhesive properties can be well exhibited. The tackifying resin containing an aromatic ring can be used alone or in combination of two or more.

[0094] Phenolic tackifying resins are preferred examples of tackifying resins containing aromatic rings. Compared to other tackifying resins (such as rosin-based tackifying resins), phenolic tackifying resins tend to have superior compatibility with polyester polymers. Examples of phenolic tackifying resins include terpene phenol resins, hydrogenated terpene phenol resins, alkylphenol aldehyde resins, and rosin phenol resins. Phenolic tackifying resins can be used alone or in combination of two or more.

[0095] Here, terpene phenol resin refers to a polymer containing terpene residues and phenol residues. It encompasses both copolymers of terpenes and phenolic compounds (terpene-phenol copolymer resins) and resins obtained by modifying terpenes, their homopolymers, or copolymers with phenol (phenol-modified terpene resins). Preferred examples of terpenes constituting such terpene phenol resins include monoterpenes such as α-pinene, β-pinene, and limonene (including d-form, l-form, and d / l-form (terpinene)). Hydrogenated terpene phenol resin refers to a hydrogenated terpene phenol resin having a structure obtained by hydrogenating such a terpene phenol resin. It is sometimes also called hydrogenated terpene phenol resin.

[0096] Alkylphenol resins are resins obtained from alkylphenols and formaldehyde (oil-based phenolic resins). Examples of alkylphenol resins include phenolic varnish type and methyl phenolic type.

[0097] Rosin phenol resins are typically phenol-modified products of rosin or various rosin derivatives (including rosin esters, unsaturated fatty acid-modified rosin, and unsaturated fatty acid-modified rosin esters). Examples of rosin phenol resins include those obtained by methods such as adding phenol to rosin or various rosin derivatives with an acid catalyst and then performing thermal polymerization.

[0098] Among the above-mentioned phenolic tackifying resins, terpene phenol resins, hydrogenated terpene phenol resins, and alkylphenol resins are preferred, terpene phenol resins and hydrogenated terpene phenol resins are more preferred, and terpene phenol resins are the most preferred.

[0099] The technology disclosed herein can preferably be implemented in a manner where about 25% by weight or more (more preferably about 30% by weight or more) of the total amount of tackifying resin is a phenolic tackifying resin (e.g., a terpene phenolic resin). It is also possible that about 50% by weight or more of the total amount of tackifying resin is a phenolic tackifying resin, or about 80% by weight or more (e.g., about 90% by weight or more) of the total amount of tackifying resin is a phenolic tackifying resin. Furthermore, it is also possible that substantially all of the tackifying resin (e.g., about 95% by weight or more and 100% by weight or less, further about 99% by weight or more and 100% by weight or less) is a phenolic tackifying resin.

[0100] As a tackifying resin having aromatic rings within the molecule, a tackifying resin with a high aromatic ring ratio is preferred. Among tackifying resins having phenol as aromatic rings, a tackifying resin with a high phenol ratio is preferred. By using a tackifying resin with a high aromatic ring ratio (e.g., phenol ratio), superior shear adhesion is easily obtained. Furthermore, superior resilience and high-temperature holding power are easily obtained. The aromatic ring ratio (e.g., phenol ratio) of the tackifying resin is, for example, 10% by weight or more, preferably 15% by weight or more from the viewpoint of resilience, more preferably 20% by weight or more, further preferably 25% by weight or more, and particularly preferably 30% by weight or more. The upper limit of the aromatic ring ratio (e.g., phenol ratio) of the tackifying resin is, for example, 65% by weight or less. From the viewpoint of adhesive strength, the upper limit of the aromatic ring ratio of the tackifying resin can be 50% by weight or less, 40% by weight or less, or 35% by weight or less.

[0101] In this specification, the aromatic ring ratio (e.g., phenol ratio) of the tackifying resin refers to the ratio measured by a nuclear magnetic resonance (NMR) instrument. 1 The aromatic ring ratio (e.g., phenol ratio) calculated by H-NMR spectroscopy. For example, in the case where the tackifying resin has the chemical structure shown below, it is considered that... 1 In the H-NMR spectrum, the peaks with chemical shifts between 7.5 ppm and 6.3 ppm originate from the phenol skeleton, while the peaks between 5.6 ppm and 0.1 ppm originate from the pinene skeleton.

[0102]

[0103] By setting the total integral value of the former peak as A and the total integral value of the latter peak as B, the molar ratio of the phenolic skeleton to the pinene skeleton in the tackifying resin can be calculated by dividing them by the number of H atoms contained in the repeating unit of each skeleton.

[0104] Molar ratio [phenol skeleton : pinene skeleton] = [A / 3 : B / 16]

[0105] Next, by multiplying the molecular weights of phenol (molecular weight 94.1) and pinene (molecular weight 136.2) by the calculated molar ratio, the weight ratio of the phenol skeleton to the pinene skeleton in the tackifying resin can be calculated.

[0106] Weight ratio [phenol skeleton: pinene skeleton] = [(A / 3) × 94.1 : (B / 16) × 136.2]

[0107] Furthermore, if the weight ratio of the phenol skeleton is set as a and the weight ratio of the pinene skeleton is set as b, the aromatic ring ratio (phenol ratio) of the above-mentioned tackifying resin can be calculated by the following formula.

[0108] Aromatic ring ratio (%) = 100 × (a / (a+b))

[0109] As an NMR device, for example, the model name "AVANCE III-400" (manufactured by Bruker Biospin) can be used. More specifically, 1 H-NMR spectroscopy measurements can be performed under the following conditions. The same method is used in the examples described later.

[0110] [ 1 [H-NMR determination]

[0111] Observation frequency: 400MHz

[0112] Measurement temperature: 23℃

[0113] Solvent used for determination: 1,1,2,2-tetrachloroethane-d2 (TCE-d2)

[0114] Measured concentration: 33 mg / mL

[0115] There is no particular limitation on the softening point of the tackifying resin containing aromatic rings. From the viewpoint of improving cohesiveness, in some embodiments, it is appropriate for the softening point (softening temperature) of the tackifying resin containing aromatic rings to be about 50°C or higher, and it is preferable to use a tackifying resin containing aromatic rings with a softening point (softening temperature) of about 80°C or higher (preferably about 100°C or higher, for example, about 115°C or higher). In some preferred embodiments, the softening point of the tackifying resin containing aromatic rings used may be about 120°C or higher (for example, 135°C or higher or 145°C or higher). The technology disclosed herein can preferably be implemented in a manner where the tackifying resin containing aromatic rings having the above-mentioned softening point accounts for more than 50% by weight (more preferably more than 70% by weight, for example, more than 90% by weight) of the total tackifying resin contained in the adhesive layer. In a more preferred embodiment, a terpene phenolic resin with a softening point of about 120°C or higher (more preferably 135°C or higher, for example, 145°C or higher) can be used. There is no particular limitation on the upper limit of the softening point of the tackifying resin containing aromatic rings. From the viewpoint of adhesive strength, in some methods, it is preferable to use a tackifying resin containing aromatic rings with a softening point of about 200°C or less (more preferably about 180°C or less, and even more preferably less than 160°C, for example, 155°C or less or 150°C or less). It should be noted that the softening point of the tackifying resin can be determined according to the softening point test method (ring and ball method) specified in JIS K2207.

[0116] The content of the tackifying resin containing aromatic rings relative to 100 parts by weight of the polyester polymer can be greater than 0 parts by weight, for example, and can be about 3 parts by weight or more (e.g., about 5 parts by weight or more). In some preferred embodiments, the content of the tackifying resin containing aromatic rings relative to 100 parts by weight of the polyester polymer is about 10 parts by weight or more, more preferably about 20 parts by weight or more, even more preferably about 30 parts by weight or more, and particularly preferably about 35 parts by weight or more. There is a tendency that the more tackifying resin containing aromatic rings is used, the easier it is to obtain excellent shear adhesive strength. There is no particular upper limit to the content of the tackifying resin containing aromatic rings. From the viewpoint of compatibility and adhesiveness with the polyester polymer, in some embodiments, it is generally appropriate for the content of the tackifying resin containing aromatic rings to be about 120 parts by weight or less relative to 100 parts by weight of the polyester polymer, preferably less than 80 parts by weight, more preferably about 70 parts by weight or less (e.g., about 50 parts by weight or less). For example, for polyester polymers with a Tg below 0°C, using a tackifying resin containing aromatic rings in the above-mentioned range is effective.

[0117] The adhesive layer disclosed herein, without impairing the effects of the invention, may optionally contain tackifying resins without aromatic rings, in addition to tackifying resins containing aromatic rings. As the tackifying resin without aromatic rings, one or more of a variety of known tackifying resins selected from terpene tackifying resins, modified terpene tackifying resins, rosin tackifying resins, hydrocarbon tackifying resins, epoxy tackifying resins, polyamide tackifying resins, elastomer tackifying resins, ketone tackifying resins, etc., may be used.

[0118] In some methods, from the viewpoint of improving the overall biomass yield of the adhesive layer, it is preferable to use a plant-derived tackifying resin (plant-based tackifying resin) as the aforementioned tackifying resin. A plant-based tackifying resin is a resin whose components are at least partially derived from plants; it can also be a resin whose components are entirely derived from plants, or a resin whose components are partly derived from plants and partly from fossil resources. Examples of plant-based tackifying resins include: the aforementioned rosin-based tackifying resins, terpene-based tackifying resins, terpene phenol resins, hydrogenated terpene phenol resins, rosin phenol resins, etc. One type of plant-based tackifying resin can be used alone or in combination of two or more. In some methods, the proportion of plant-based tackifying resin in the total amount of tackifying resin contained in the adhesive layer can be 30% by weight or more (e.g., 50% by weight or more, typically 80% by weight or more), and the proportion of plant-based tackifying resin in the total amount of tackifying resin can be 90% by weight or more (e.g., 95% by weight or more, typically 99% by weight to 100% by weight). The technology disclosed herein can be implemented in a manner that substantially does not contain any tackifying resins other than plant-based tackifying resins.

[0119] The total amount (total content) of tackifying resin relative to 100 parts by weight of the polyester polymer can, for example, be greater than 0 parts by weight, and can be about 3 parts by weight or more (e.g., about 5 parts by weight or more). In some preferred embodiments, the total amount of tackifying resin relative to 100 parts by weight of the polyester polymer is about 10 parts by weight or more, more preferably about 20 parts by weight or more, even more preferably about 30 parts by weight or more, and particularly preferably about 35 parts by weight or more. There is a tendency that the more tackifying resin used, the easier it is to obtain excellent adhesive strength. There is no particular upper limit to the total amount of tackifying resin. From the viewpoint of compatibility and adhesiveness with the polyester polymer, in some embodiments, it is generally appropriate for the total amount of tackifying resin to be about 120 parts by weight or less relative to 100 parts by weight of the polyester polymer, preferably less than 80 parts by weight, and more preferably about 70 parts by weight or less (e.g., about 50 parts by weight or less). For example, for polyester polymers with a Tg of 0°C or less, using tackifying resin in the above-mentioned range is effective.

[0120] (Cross-linking agent)

[0121] The adhesive composition used in forming the adhesive layer includes a crosslinking agent without aromatic rings (a crosslinking agent without aromatic rings) as a crosslinking agent. By using a crosslinking agent without aromatic rings in a composition containing a polyester polymer containing aromatic rings and a tackifying resin, a good crosslinking structure (crosslinking reaction) can be obtained, and the role of the aromatic rings contained in the polyester polymer and the tackifying resin can be appropriately utilized. The adhesive layer in the disclosed technology may contain the aforementioned crosslinking agent in the form after the crosslinking reaction, in the form before the crosslinking reaction, in the form after a partial crosslinking reaction, in the intermediate form, or in a composite form. The aforementioned crosslinking agent is usually only included in the adhesive layer in the form after the crosslinking reaction. It should be noted that the crosslinking agent used in the crosslinking of the polyester polymer can also function as a chain extender.

[0122] There are no particular restrictions on the type of crosslinking agent, as long as it has a structure without aromatic rings. A crosslinking agent without aromatic rings can be appropriately selected from conventionally known crosslinking agents. Examples of such crosslinking agents without aromatic rings include: isocyanate crosslinking agents, epoxy crosslinking agents, etc. Crosslinking agents include zopyridine crosslinking agents, melamine crosslinking agents, and metal chelate crosslinking agents. Crosslinking agents without aromatic rings can be used alone or in combination of two or more. Isocyanate crosslinking agents are preferred. By using isocyanate crosslinking agents without aromatic rings, the degree of crosslinking can be effectively increased in adhesive compositions containing polyester polymers and tackifying resins with less resistance to crosslinking.

[0123] Examples of isocyanate crosslinking agents include polyfunctional isocyanate compounds (including substances having an isocyanurate structure) where each molecule has an average of two or more isocyanate groups. These polyfunctional isocyanate compounds can be polymers (e.g., dimers or trimers) of difunctional or trifunctional or higher isocyanates, derivatives (e.g., addition reaction products of polyols with two or more molecules of polyfunctional isocyanates), polymers, etc. Examples include: isocyanurate bodies of hexamethylene diisocyanate (trimeric adducts of the isocyanurate structure), reaction products of trimethylolpropane and hexamethylene diisocyanate, polyether polyisocyanates, polyester polyisocyanates, and other polyfunctional isocyanate compounds. The aforementioned isocyanate crosslinking agents can be used alone or in combination of two or more.

[0124] Examples of polyfunctional isocyanates that do not contain aromatic rings include aliphatic polyisocyanates and alicyclic polyisocyanates.

[0125] Specific examples of aliphatic polyisocyanates include: 1,2-ethylidene diisocyanate; 1,2-butylidene diisocyanate, 1,3-butylidene diisocyanate, 1,4-butylidene diisocyanate, and other butylidene diisocyanates; 1,2-hexylidene diisocyanate, 1,3-hexylidene diisocyanate, 1,4-hexylidene diisocyanate, 1,5-hexylidene diisocyanate, 1,6-hexylidene diisocyanate, 2,5-hexylidene diisocyanate, and other hexylidene diisocyanates; 2-methyl-1,5-pentane diisocyanate, 3-methyl-1,5-pentane diisocyanate, lysine diisocyanate, etc.

[0126] Specific examples of alicyclic polyisocyanates include: isophorone diisocyanate; cyclohexyl diisocyanates such as 1,2-cyclohexyl diisocyanate, 1,3-cyclohexyl diisocyanate, and 1,4-cyclohexyl diisocyanate; cyclopentyl diisocyanates such as 1,2-cyclopentyl diisocyanate and 1,3-cyclopentyl diisocyanate; hydrogenated diphenylmethylene diisocyanate, hydrogenated toluene diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated tetramethylxylene diisocyanate, and 4,4'-dicyclohexylmethane diisocyanate.

[0127] As a preferred example of the aforementioned isocyanate without aromatic rings, aliphatic isocyanate compounds can be cited. The technology disclosed herein is particularly preferably implemented using aliphatic isocyanate compounds as crosslinking agents in the formation of polyester polymers and tackifying resins both having aromatic rings.

[0128] In some methods, it is preferable to use two or more crosslinking agents with different numbers of functional groups (suitably isocyanate crosslinking agents). By using two or more crosslinking agents with different numbers of functional groups, it is easy to balance multiple properties (e.g., shear adhesion, resilience, etc.). It should be noted that the above-mentioned functional groups refer to crosslinking reactive groups, for example, isocyanate groups in the above-mentioned polyfunctional isocyanate compounds. In some preferred methods, one or more bifunctional crosslinking agents and one or more trifunctional or higher crosslinking agents (e.g., trifunctional crosslinking agents) can be used together as crosslinking agents. By using bifunctional and trifunctional or higher crosslinking agents together, it is easy to obtain adhesives with excellent resilience, and it is easy to balance shear adhesion and resilience. It is believed that bifunctional crosslinking agents mainly function as chain extenders, which helps to improve resilience by lengthening the polyester polymer during the curing of the adhesive composition. On the other hand, by using trifunctional or higher crosslinking agents, the cohesiveness of the adhesive is improved, resulting in shear adhesion. It should be noted that the technology disclosed herein is not limited to the above explanation. As a difunctional or trifunctional or higher crosslinking agent, difunctional and trifunctional or higher crosslinking agents can be used without particular limitation. In some preferred embodiments, isocyanate compounds that do not contain aromatic rings are preferably used as difunctional or trifunctional or higher crosslinking agents.

[0129] In the use of a bifunctional crosslinking agent as a crosslinking agent, there is no particular limitation on the amount of the bifunctional crosslinking agent used. For example, from the viewpoint of obtaining the desired effect of the bifunctional crosslinking agent, it is appropriate for the amount of the bifunctional crosslinking agent used to be about 0.01 parts by weight or more relative to 100 parts by weight of the polyester polymer, preferably about 0.1 parts by weight or more, more preferably about 0.5 parts by weight or more, even more preferably about 0.8 parts by weight or more, and may also be about 1.5 parts by weight or more, or may also be about 3 parts by weight or more. In addition, it is generally appropriate for the amount of the bifunctional crosslinking agent used to be about 10 parts by weight or less relative to 100 parts by weight of the polyester polymer, preferably about 7 parts by weight or less, and may be 4 parts by weight or less.

[0130] In the method of using a trifunctional or higher crosslinking agent as the crosslinking agent, there is no particular limitation on the amount of the trifunctional or higher crosslinking agent used. For example, from the viewpoint of obtaining the effect of using a trifunctional or higher crosslinking agent, it is appropriate for the amount of the trifunctional or higher crosslinking agent used to be about 0.01 parts by weight or more relative to 100 parts by weight of the polyester polymer, preferably about 0.1 parts by weight or more, more preferably about 0.5 parts by weight or more, further preferably about 1 part by weight or more, and particularly preferably about 2 parts by weight or more (e.g., about 2.5 parts by weight or more). By using an appropriate amount of trifunctional or higher crosslinking agent, the cohesive strength is improved, and excellent properties (such as shear adhesion) are easily obtained. In addition, it is generally appropriate for the amount of the trifunctional or higher crosslinking agent used to be about 8 parts by weight or less relative to 100 parts by weight of the polyester polymer, preferably about 5 parts by weight or less, and can be 4 parts by weight or less.

[0131] In the combined use of bifunctional and trifunctional or higher-functional crosslinking agents, the ratio of bifunctional to trifunctional or higher-functional crosslinking agents is appropriately set to achieve a balanced combination of various target adhesive properties (shear strength, adhesive strength, high-temperature retention, resilience, etc.), and is not limited to a specific range. The amount C of the trifunctional or higher-functional crosslinking agent... B Relative to the amount C of the bifunctional crosslinking agent A The ratio (C) B / C A For example, if it is above 0.1, from the perspective of improving cohesion, C B / C A A value of 0.3 or higher is appropriate, preferably 0.5 or higher, more preferably 0.8 or higher, and can also be 1.5 or higher, or even 2 or higher. Furthermore, the above ratio (C) B / C A For example, if the value is below 10, from the perspective of improving resilience, the above ratio (C) is... B / C A The value is preferably 7 or less, more preferably 5 or less, and may also be 4 or less, 2.5 or less, or 1.5 or less.

[0132] There is no particular limitation on the amount of crosslinking agent without aromatic rings used. For example, relative to 100 parts by weight of the polyester polymer, the amount of crosslinking agent without aromatic rings used can be about 0.005 parts by weight or more (e.g., about 0.01 parts by weight or more, typically about 0.1 parts by weight or more). From the viewpoint of improving cohesiveness, it is generally appropriate to use about 0.5 parts by weight or more relative to 100 parts by weight of the polyester polymer, preferably about 1 part by weight or more, more preferably about 2 parts by weight or more (e.g., more than 2 parts by weight), and even more preferably 2.5 parts by weight or more. In addition, relative to 100 parts by weight of the polyester polymer, it is generally appropriate to use about 12 parts by weight or less, for example, about 10 parts by weight or less, about 8 parts by weight or less, preferably about 5 parts by weight or less. According to the technology disclosed herein, by using the crosslinking agent amount limited as described above, it is possible to obtain cohesiveness that preferably exhibits high shear strength, resilience, etc. The amount of crosslinking agent without aromatic rings used is more preferably 4 parts by weight or less, and even more preferably about 3.5 parts by weight or less, relative to 100 parts by weight of polyester polymer.

[0133] In the use of isocyanate crosslinking agents without aromatic rings, the amount used is not particularly limited. The amount of isocyanate crosslinking agent without aromatic rings used relative to 100 parts by weight of the polyester polymer can be, for example, about 0.5 parts by weight or more and about 10 parts by weight or less. From the viewpoint of improving cohesiveness, the amount of isocyanate crosslinking agent without aromatic rings used relative to 100 parts by weight of the polyester polymer is generally appropriate to be about 1 part by weight or more, preferably about 2 parts by weight or more (e.g., more than 2 parts by weight), more preferably about 2.5 parts by weight or more, further preferably 2.8 parts by weight or more, and can be about 3.5 parts by weight or more, about 4.0 parts by weight or more, or 4.5 parts by weight or more. Furthermore, the amount of isocyanate crosslinking agent without aromatic rings used relative to 100 parts by weight of the polyester polymer is generally appropriate to be about 8 parts by weight or less, preferably about 5 parts by weight or less. According to the technology disclosed herein, by using the above-limited amount of isocyanate crosslinking agent without aromatic rings, it is possible to obtain cohesive strengths such as shear adhesion and resilience. The amount of isocyanate crosslinking agent without aromatic rings used is more preferably 4.5 parts by weight or less, more preferably about 4.2 parts by weight or less, particularly preferably 3.8 parts by weight or less (e.g., 3.5 parts by weight or less), and may also be about 3.2 parts by weight or less, relative to 100 parts by weight of polyester polymer.

[0134] The adhesive compositions disclosed herein, without impairing the effects of the invention, may optionally contain a crosslinking agent containing an aromatic ring (the aromatic ring-containing crosslinking agent) in addition to a crosslinking agent that does not contain an aromatic ring. There are no particular limitations on the type of crosslinking agent containing the aromatic ring; for example, isocyanate crosslinking agents, epoxy crosslinking agents, etc., can be used. Crosslinking agents containing aromatic rings, such as aziridine crosslinking agents, melamine crosslinking agents, and metal chelate crosslinking agents, are included. These crosslinking agents can be used alone or in combination of two or more.

[0135] There is no particular limitation on the total amount of crosslinking agent used. For example, relative to 100 parts by weight of the polyester polymer, the total amount of crosslinking agent used can be about 0.005 parts by weight or more (e.g., about 0.01 parts by weight or more, typically about 0.1 parts by weight or more). From the viewpoint of improving cohesion, relative to 100 parts by weight of the polyester polymer, it is generally appropriate to have a total amount of crosslinking agent used of about 0.5 parts by weight or more, preferably about 1 part by weight or more, more preferably about 2 parts by weight or more (e.g., more than 2 parts by weight), and even more preferably 2.5 parts by weight or more. In addition, relative to 100 parts by weight of the polyester polymer, it is generally appropriate to have a total amount of crosslinking agent used of about 12 parts by weight or less, for example, about 10 parts by weight or less, about 8 parts by weight or less, and preferably about 5 parts by weight or less. According to the technology disclosed herein, good cohesion can be obtained by using the crosslinking agent amount limited as above. Relative to 100 parts by weight of the polyester polymer, it is more preferably 4 parts by weight or less, and even more preferably about 3.5 parts by weight or less.

[0136] (Cross-linking catalyst)

[0137] In the technology disclosed herein, in order to carry out the crosslinking reaction more effectively, in addition to using the aforementioned crosslinking agent, a crosslinking catalyst is preferably used. Examples of crosslinking catalysts include: zirconium-containing compounds such as zirconium acetylacetonate, zirconium monoacetylacetonate, zirconium ethylacetoacetate, and zirconium octanoate compounds (zirconium-containing catalysts); tin-containing compounds such as dioctyltin dilaurate, dibutyltin dilaurate, dibutyltin diacetate, dibutyltin diacetylacetonate, tetra-n-butyltin, trimethyltin hydroxide, and butyltin oxide (tin-containing catalysts); aluminum-containing compounds such as aluminum sec-butoxyaluminum, aluminum triacetylacetonate, aluminum diethylacetylacetate, and aluminum triethylacetylacetate (aluminum-containing catalysts); iron-containing compounds such as NACEM iron(III) (iron triacetylacetonate) (iron-containing catalysts); titanium-containing compounds such as tetraisopropyl titanate, tetra-n-butyl titanate, butyl titanate dimer, tetraoctyl titanate, titanium acetylacetonate, titanium tetraacetylacetonate, and titanium ethylacetoacetate (titanium-containing catalysts); and organometallic catalysts. Crosslinking catalysts can be used alone or in combination of two or more.

[0138] In some preferred embodiments, from the viewpoint of environmental impact and safety, the aforementioned crosslinking catalyst is free of tin-containing compounds. By using tin-free compounds as crosslinking catalysts, the amount of tin-containing compounds (typically organotin) used in the adhesive can be reduced. According to the adhesive compositions disclosed herein, good crosslinking structures can be formed with good productivity without using tin-containing crosslinking catalysts, which typically have an excellent reaction rate tendency. Furthermore, in some embodiments, the crosslinking catalyst is free of iron-containing catalysts. For example, in applications requiring transparency and optical properties in the adhesive, it is preferable to avoid using iron-containing compounds that may cause discoloration of the adhesive.

[0139] There is no particular limitation on the amount of crosslinking catalyst used. For example, the amount of crosslinking catalyst used relative to 100 parts by weight of the polyester polymer can be about 0.001 parts by weight or more, which is appropriate, or about 0.05 parts by weight or more (e.g., 0.10 parts by weight or more). Furthermore, for example, the amount of crosslinking catalyst used relative to 100 parts by weight of the polyester polymer can be about 3 parts by weight or less, which is appropriate, or about 1 part by weight or less, or about 0.3 parts by weight or less.

[0140] (Hydrolysis resistant agent)

[0141] Furthermore, the adhesive compositions disclosed herein may contain a hydrolysis-resistant agent (also known as a hydrolysis inhibitor). By adding a hydrolysis-resistant agent, hydrolysis reactions in the adhesive can be suppressed, easily resulting in good durability. There are no particular limitations on the hydrolysis-resistant agent; known and even conventionally used hydrolysis-resistant agents can be used. Examples include: those containing... Compounds with an oxazolinyl group, compounds containing an epoxy group, and compounds containing a carbodiimide group are all acceptable. Compounds containing a carbodiimide group are preferred. Hydrolysis resistant agents can be used alone or in combination of two or more.

[0142] Examples of compounds containing a carbodiimide group include: dicyclohexylcarbodiimide, diisopropylcarbodiimide, dimethylcarbodiimide, diisobutylcarbodiimide, dioctylcarbodiimide, tert-butylisopropylcarbodiimide, diphenylcarbodiimide, ditert-butylcarbodiimide, di-β-naphthylcarbodiimide, and monofunctional cyclic carbodiimides. Here, a monofunctional cyclic carbodiimide refers to a compound having a single carbodiimide group within its molecular structure, obtained by bonding the first nitrogen atom of the carbodiimide group to a second nitrogen atom through a bonding group composed of an aliphatic group, an alicyclic group, an aromatic group, or a combination thereof. It should be noted that the aforementioned bonding group may contain heteroatoms or substituents. Preferred examples of compounds containing a carbodiimide group include: dicyclohexylcarbodiimide, diisopropylcarbodiimide, and monofunctional cyclic carbodiimides.

[0143] There is no particular limitation on the amount of hydrolysis-resistant agent (suitably a compound containing a carbodiimide group). However, to optimally utilize the effect of the hydrolysis-resistant agent, it is appropriate to use about 0.05 parts by weight or more, preferably about 0.1 parts by weight or more, and for example, about 0.3 parts by weight or more, relative to 100 parts by weight of the polyester polymer. The upper limit for the aforementioned amount of hydrolysis-resistant agent relative to 100 parts by weight is, for example, about 5 parts by weight or less, preferably about 3 parts by weight or less, and for example, about 1 part by weight or less.

[0144] (Other additives)

[0145] In addition to the components described above, the adhesive composition may, as needed, include various additives commonly found in the adhesive field, such as leveling agents, fillers, plasticizers, softeners, colorants (pigments, dyes, etc.), antistatic agents, anti-aging agents, ultraviolet absorbers, antioxidants, and light stabilizers. These additives can be made from conventionally known substances using conventional methods and are not a feature of this invention; therefore, detailed descriptions are omitted.

[0146] (Adhesive composition)

[0147] The adhesive layer (a layer composed of adhesive) disclosed herein is formed from an adhesive composition comprising the aforementioned polyester polymer, tackifying resin, and crosslinking agent. From the viewpoint of adhesive properties, a solvent-based adhesive composition in which the adhesive is contained within an organic solvent is preferred as the adhesive composition. Toluene, ethyl acetate, or other organic solvents can be used as the organic solvent.

[0148] As described above, according to this specification, an adhesive composition is provided that contains one or more of the components that may be included in the adhesive layer disclosed herein. Specifically, the adhesive composition contains an aromatic ring-containing polyester polymer in which more than 50% of the carbon composition is derived from biomass, and may also contain an aromatic ring-containing tackifying resin and an aromatic ring-free crosslinking agent. According to this adhesive composition, dependence on fossil-based materials can be reduced, and an adhesive capable of exhibiting high shear adhesion can be formed. The above-mentioned adhesive composition may also contain components such as a crosslinking catalyst and a hydrolysis-resistant agent. Details regarding the components that may be included in the above-mentioned adhesive composition are already described in the adhesive layer description, and therefore will not be repeated.

[0149] (Formation of the adhesive layer)

[0150] The adhesive layer can be formed from the adhesive composition using conventionally known methods. For example, in the case of a substrate-free double-sided adhesive sheet, after applying the adhesive composition to a peelable surface (peel surface), the adhesive composition is cured to form an adhesive layer on that surface, thereby forming the adhesive sheet. Alternatively, in the case of an adhesive sheet with a substrate, a method of forming the adhesive layer by directly applying (typically coating) the adhesive composition to the substrate and curing it (direct method) is preferred. Another method is to form an adhesive layer by applying the adhesive composition to a peelable surface (peel surface) and curing it, and then transferring the adhesive layer to the substrate (transfer method). The peel surface can be the surface of a release liner, the back side of the substrate after peeling, etc. Furthermore, the curing of the adhesive composition can be performed by subjecting the adhesive composition to curing treatments such as drying, crosslinking, polymerization, and cooling. Two or more curing treatments can be performed simultaneously or in stages. It should be noted that the adhesive layer disclosed herein is typically formed continuously, but is not limited to this method; for example, it can be an adhesive layer formed in a regular or irregular pattern such as dots or stripes.

[0151] The adhesive composition can be coated using known and conventional coating machines such as gravure roller coaters, reverse roller coaters, licker coaters, dip roller coaters, die coaters, bar coaters, doctor blade coaters, and spray coaters. Alternatively, the adhesive composition can be coated using methods such as dip coating or curtain coating.

[0152] The drying of the adhesive composition can be carried out at room temperature or under heat. From the viewpoint of promoting crosslinking reactions and improving manufacturing efficiency, drying the adhesive composition is preferably carried out under heat. The drying temperature can be, for example, from about 40°C to about 150°C, and is typically preferred from about 40°C to about 130°C. After drying, the adhesive composition is preferably further cured for purposes such as regulating component movement within the adhesive layer, initiating crosslinking reactions, and relaxing any strain that may exist within the substrate or adhesive layer. The curing conditions are not particularly limited, and can be, for example, below about 70°C (typically about 40°C to about 70°C) for more than one day (e.g., more than three days).

[0153] (Adhesive layer thickness)

[0154] In the adhesive sheet disclosed herein, the thickness of the adhesive layer is not particularly limited and can be appropriately selected according to the purpose. The thickness of the adhesive layer can be, for example, from about 2 μm to about 500 μm. From the viewpoint of adhesiveness to the adhered objects, a thickness of 3 μm or more is generally suitable, and preferably 5 μm or more. From the viewpoint of easily achieving an adhesive sheet with higher shear adhesive strength, in some embodiments, the thickness of the adhesive layer can be, for example, 8 μm or more, preferably 12 μm or more, or 15 μm or more, or even 18 μm or more. Furthermore, from the viewpoint of thinning the adhesive sheet, the thickness of the adhesive layer can be, for example, 200 μm or less, 150 μm or less, 100 μm or less, 70 μm or less, 50 μm or less, or 30 μm or less. In embodiments that place greater emphasis on thinness, the thickness of the adhesive layer can be, for example, 25 μm or less, or 22 μm or less. When the adhesive sheet disclosed herein is a double-sided adhesive sheet with adhesive layers on both sides of a substrate, the thickness of each adhesive layer can be the same or different.

[0155] (Biomass ratio of the adhesive layer)

[0156] The technology disclosed herein is implemented using an adhesive comprising a polyester polymer with a biomass percentage of 50% or more, thus the adhesive layer (and the adhesive composition, hereinafter the same) has a biomass percentage of a specified value or higher. While not particularly limited, the biomass percentage of the adhesive layer can be about 30% or more (e.g., greater than 30%), about 40% or more is suitable, and preferably 50% or more. A high biomass percentage of the adhesive layer means less use of fossil resources such as petroleum. By designing the adhesive layer to have a high biomass percentage, the overall dependence of the adhesive layer on fossil resources can be reduced. For example, the biomass percentage of the adhesive layer can be 55% or more, 60% or more, 70% or more, or 75% or more. The upper limit of the biomass percentage is defined as 100%, but the components in the adhesive layer disclosed herein can include materials from fossil resources, so the biomass percentage can typically be less than 100%. From the viewpoint of easily obtaining performance (e.g., shear strength) suitable for portable electronic device applications, in some cases the biomass content of the adhesive layer can be less than 90%, and in cases where adhesive performance is given more importance, the biomass content of the adhesive layer can be less than 80% or less than 70%.

[0157] It should be noted that the biomass percentage of the adhesive layer, i.e., the proportion of carbon from biomass in the total carbon content of the adhesive layer, can be estimated from the carbon isotope content of mass number 14 as determined according to ASTM D6866. The biomass percentage of the substrate and the adhesive sheet described later can also be estimated using the same method.

[0158] <Substrate>

[0159] The adhesive sheet disclosed herein can be in the form of an adhesive sheet with an adhesive layer on one or both sides of a substrate. Various sheet-like substrates can be used as the substrate, such as resin films, paper, cloth, rubber sheets, foam sheets, metal foils, and composites thereof. In the field of electronic devices, substrates that are not easily a source of dust (e.g., fine fibers or particles such as paper dust) are preferred. From this viewpoint, substrates free of fibrous materials such as paper and cloth are preferred; for example, resin films, rubber sheets, foam sheets, metal foils, and composites thereof are preferred.

[0160] Examples of resin films include: polyester films such as polyethylene terephthalate (PET) and polyethylene naphthalate; vinyl chloride resin films; polyolefin films such as polyethylene (PE), polypropylene (PP), ethylene-propylene copolymer, and ethylene-butene copolymer; vinylidene chloride resin films; vinyl acetate resin films; polystyrene films; polyacetal films; polyimide films; polyamide films; fluorinated resin films; and cellophane. Examples of rubber sheets include: natural rubber sheets and butyl rubber sheets. Examples of foamed sheets include: foamed polyurethane sheets and foamed polyolefin sheets. Examples of metal foils include: aluminum foil and copper foil.

[0161] Using a resin film as the aforementioned substrate is appropriate. Resin films are preferred due to their excellent dimensional stability, thickness accuracy, economy (cost), processability, and tensile strength. Furthermore, resin films (such as polyester films like PET films described later) are recyclable; therefore, regardless of whether plant-derived materials are used, continuous reprocessing is possible by reusing the used resin film, thus reducing environmental impact. Resin films that are recyclable, or already recycled resin films, are also called reusable films. This recyclability of resin films can be applied to resin films used for the aforementioned release liner. It should be noted that in this specification, "resin film" typically refers to a non-porous membrane, as opposed to the concept of so-called nonwoven or woven fabrics.

[0162] In some cases, from the viewpoint of strength and processability, polyester film is preferred as the substrate. Typically, polyester resins comprising a polyester obtained by polycondensation of a dicarboxylic acid and a diol are used as the main component.

[0163] Examples of dicarboxylic acids constituting the aforementioned polyesters include: phthalic acid, isophthalic acid, terephthalic acid, 2-methylterephthalic acid, 5-sulfonyl isophthalic acid, 4,4'-biphenyl dicarboxylic acid, 4,4'-diphenyl ether dicarboxylic acid, 4,4'-diphenyl ketone dicarboxylic acid, 4,4'-diphenoxyethane dicarboxylic acid, 4,4'-diphenyl sulfone dicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 2,7- Aromatic dicarboxylic acids such as naphthalenedicarboxylic acid; alicyclic dicarboxylic acids such as 1,2-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, and 1,4-cyclohexanedicarboxylic acid; aliphatic dicarboxylic acids such as malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, octanoic acid, azelaic acid, sebacic acid, and dodecanoic acid; unsaturated dicarboxylic acids such as maleic acid, maleic anhydride, and fumaric acid; and derivatives of these substances (e.g., lower alkyl esters of the above dicarboxylic acids such as terephthalic acid). These substances can be used alone or in combination of two or more.

[0164] Examples of diols constituting the aforementioned polyesters include: aliphatic diols such as ethylene glycol, diethylene glycol, polyethylene glycol, propylene glycol, polypropylene glycol, 1,3-propanediol, 1,5-pentanediol, neopentanediol, 1,4-butanediol, 1,6-hexanediol, 1,8-octanediol, and polyoxytetramethylene glycol; alicyclic diols such as 1,2-cyclohexanediol, 1,4-cyclohexanediol, 1,1-cyclohexanediethanol, and 1,4-cyclohexanediethanol; and aromatic diols such as benzenediethanol, 4,4'-dihydroxybiphenyl, 2,2-bis(4'-hydroxyphenyl)propane, and bis(4-hydroxyphenyl)sulfone. These can be used alone or in combination of two or more. From the viewpoint of transparency, aliphatic diols are preferred, and ethylene glycol is particularly preferred. The proportion of aliphatic diols (preferably ethylene glycol) in the diols constituting the above-mentioned polyester is preferably 50% by weight or more (e.g., 80% by weight or more, typically 95% by weight or more). The above-mentioned diols may consist substantially entirely of ethylene glycol. As the above-mentioned ethylene glycol, ethylene glycol derived from biomass (typically biomass ethylene glycol obtained from biomass ethanol) is preferably used. For example, the proportion of biomass-derived ethylene glycol in the ethylene glycol constituting the above-mentioned polyester may be, for example, 50% by weight or more, preferably 75% by weight or more, 90% by weight or more, or 95% by weight or more. The above-mentioned ethylene glycol may be substantially entirely derived from biomass.

[0165] Examples of polyester resin films include: polyethylene terephthalate (PET) film, polybutylene terephthalate (PBT) film, polyethylene naphthalate (PEN) film, and polybutylene naphthalate film.

[0166] When the substrate disclosed herein is a polyester film substrate, the polyester film substrate may contain polymers other than polyester in addition to polyester. Preferred examples of polymers other than polyester include materials other than polyester among various polymer materials exemplified as resin films that can constitute the substrate. When the polyester film substrate disclosed herein contains polymers other than polyester in addition to polyester, it is appropriate for the content of the polymer other than polyester to be less than 100 parts by weight relative to 100 parts by weight of polyester, preferably 50 parts by weight or less, more preferably 30 parts by weight or less, and even more preferably 10 parts by weight or less. The content of the polymer other than polyester may be 5 parts by weight or less, or 1 part by weight or less, relative to 100 parts by weight of polyester. The technology disclosed herein can preferably be implemented in a manner where 99.5% to 100% by weight of the polyester film substrate is polyester.

[0167] In other respects, from the viewpoint of strength and flexibility, polyolefin films are preferred as the aforementioned substrate. A polyolefin film is a film in which a polymer with α-olefin as the main monomer (the main component of the monomer composition) is used as the main component. The proportion of the aforementioned polymer is typically 50% by weight or more (e.g., 80% by weight or more, typically 90% to 100% by weight). Specific examples of polyolefins include: polyolefins with ethylene as the main monomer (polyethylene), polyolefins with propylene as the main monomer (polypropylene), etc. The aforementioned polyethylene can be a homopolymer of ethylene, or a copolymer of ethylene with other olefins (e.g., one or more selected from α-olefins having 3 to 10 carbon atoms), or a copolymer of ethylene with monomers other than olefins (e.g., one or more selected from olefinic unsaturated monomers such as vinyl acetate, acrylic acid, methacrylic acid, methyl acrylate, ethyl acrylate, etc.). Furthermore, the polypropylene described above can be a homopolymer of propylene, a copolymer of propylene and other olefins (e.g., one or more α-olefins selected from those having 2, 4 to 10 carbon atoms), or a copolymer of propylene and monomers other than olefins. The substrate disclosed herein may contain only one of the polyolefins described above, or it may contain two or more polyolefins.

[0168] When the substrate disclosed herein is a polyolefin film substrate, the polyolefin film substrate may contain polymers other than the aforementioned polyolefin in addition to polyolefin. Preferred examples of polymers other than the aforementioned polyolefin include materials other than polyolefin from various polymer materials exemplified as resin films that can constitute the aforementioned substrate. When the polyolefin film substrate disclosed herein contains polymers other than the aforementioned polyolefin in addition to polyolefin, it is appropriate for the content of the polymer other than polyolefin to be less than 100 parts by weight relative to 100 parts by weight of polyolefin, preferably 50 parts by weight or less, more preferably 30 parts by weight or less, and even more preferably 10 parts by weight or less. The content of the polymer other than polyolefin may be 5 parts by weight or less, or even 1 part by weight or less, relative to 100 parts by weight of polyolefin. The technology disclosed herein can preferably be implemented in a manner where 99.5% to 100% by weight of the polyolefin film substrate is polyolefin.

[0169] From the perspective of reducing the use of fossil-based materials, the substrate disclosed herein preferably includes biomass materials. There are no particular limitations on the biomass materials that can constitute the aforementioned substrate; examples include: biomass polyesters such as biomass PET and biomass polypropylene terephthalate (PTT); polylactic acid; biomass polyethylene such as biomass high-density polyethylene (HDPE), biomass low-density polyethylene (LDPE), and biomass linear low-density polyethylene (LLDPE); biomass polyolefins such as biomass polypropylene (PP); biomass poly(3-hydroxybutyrate-co-3-hydroxyhexanoate); biomass polyamides such as polyhexamethylene sebacate and poly(poly(dimethyl sebacate)); biomass polyurethanes such as biomass polyester ether urethane and biomass polyether urethane; cellulosic resins; etc. These substances can be used alone or in combination of two or more. Among these, biomass PET and biomass PTT are preferred, with biomass HDPE, biomass LDPE, biomass LLDPE, biomass PP, and biomass PET being particularly preferred. Since these biomass materials are resin materials, they are therefore preferably suitable for compositions with a resin film as the substrate. By using these biomass materials, the amount of fossil-based materials used in adhesive sheets with a resin film (preferably a polyolefin film) as the substrate can be reduced.

[0170] In adhesive sheets having a substrate, the biomass percentage of the substrate is preferably 20% or more, more preferably 35% or more. When there is a greater emphasis on reducing the use of fossil-based materials, the biomass percentage of the substrate can be, for example, 50% or more, 70% or more, 85% or more, or 90% or more. The upper limit of the above biomass percentage is 100% or less, but in some cases, considering processability, strength, etc., the biomass percentage of the substrate can be, for example, 80% or less, 60% or less, 40% or less, or less than 20%.

[0171] The substrate can be transparent, or it can have light-blocking or light-reducing properties. In some cases, a colorant can be included in the substrate (e.g., a resin film). This allows the light transmittance (light-blocking property) of the substrate to be adjusted. Adjusting the light transmittance of the substrate (e.g., vertical transmittance) can help regulate the light transmittance of both the substrate and the adhesive sheet containing it.

[0172] As a colorant, similar to colorants that can be included in the adhesive layer, conventionally known pigments and dyes can be used. There are no particular limitations on the colorant; for example, it can be a colorant in black, gray, white, red, blue, yellow, green, yellowish-green, orange, purple, gold, silver, pearlescent, etc.

[0173] The substrate can be colored by a coloring layer disposed on the surface of a base film (preferably a resin film). In a substrate comprising a base film and a coloring layer, the base film may or may not contain a colorant. The coloring layer may be disposed on any surface of the base film or on both surfaces. In a configuration where coloring layers are disposed on both surfaces of the base film, the compositions of these coloring layers may be the same or different. By configuring the coloring layer, the color and translucency of the adhesive sheet can be adjusted, and desired appearance, light blocking, and concealment can be obtained. The color of the coloring layer is not particularly limited, and various colors can be used depending on the purpose. In some embodiments, the coloring layer may be, for example, a black layer formed by black printing (e.g., a black printing layer).

[0174] The coloring layer can be formed, for example, by coating a coloring layer forming composition containing a colorant and a binder onto a base film. As the binder, materials known in the coating or printing fields can be used without particular limitation. Examples include polyurethane, phenolic resin, epoxy resin, urea melamine resin, polymethyl methacrylate, etc. The coloring layer forming composition can be, for example, solvent-based, UV-curable, thermosetting, etc. The coloring layer can be formed without particular limitation using methods traditionally employed in coloring layer formation. For example, methods for forming the coloring layer (printed layer) by gravure printing, flexographic printing, offset printing, etc., are preferred.

[0175] The coloring layer can be a single-layer structure consisting entirely of one layer, or a multi-layer structure containing two, three, or more sub-coloring layers. A multi-layer coloring layer containing two or more sub-coloring layers can be formed, for example, by repeatedly applying (e.g., printing) a coloring layer forming composition. The color and amount of colorant contained in each sub-coloring layer can be the same or different. In coloring layers used to impart light-blocking properties, a multi-layer structure is particularly advantageous from the viewpoint of improving the reliability of light leakage prevention by preventing pinhole formation.

[0176] As a coloring agent for the coloring layer, a known pigment or dye corresponding to the target color can be appropriately selected. While there are no particular limitations, examples of white pigments include titanium dioxide, zinc oxide, and lead white. Examples of black pigments include carbon black, acetylene black, pine soot, and graphite. These can be used alone or in combination of two or more.

[0177] The content of the colorant is set according to the desired color, light transmittance, etc., and is therefore not limited to a specific range. In the colored layer, it is appropriate for the content of the colorant to be about 1% by weight or more, preferably 2% by weight or more (e.g., 5% by weight or more), and it can be 15% by weight or more. In addition, it is appropriate for the content of the above-mentioned colorant to be about 65% by weight or less, preferably 30% by weight or less (e.g., 15% by weight or less), and it can be 8% by weight or less.

[0178] The overall thickness of the coloring layer is typically 0.1 μm or more, preferably 0.5 μm or more, and more preferably 0.7 μm or more. The overall thickness of the coloring layer can be about 0.8 μm or more, or about 1 μm or more. In other embodiments, from the viewpoint of obtaining sufficient light blocking properties, the overall thickness of the coloring layer can be 2 μm or more (e.g., 3 μm or more), or 4 μm or more. Furthermore, the overall thickness of the aforementioned coloring layer is typically 10 μm or less, preferably 7 μm or less, and more preferably 5 μm or less. In some embodiments, the overall thickness of the coloring layer can be about 3 μm or less, and further, about 2 μm or less. In a coloring layer comprising two or more sub-coloring layers, the thickness of each sub-coloring layer is typically preferably about 0.5 μm to about 2 μm.

[0179] Known or conventional surface treatments, such as corona discharge treatment, plasma treatment, ultraviolet irradiation treatment, acid treatment, alkali treatment, and the formation of a primer layer, can be applied to the surface of the substrate (e.g., resin film, rubber sheet, foam sheet, etc.) on which the adhesive layer is to be applied (adhesive layer side surface). Such surface treatments can be used to improve the adhesion between the substrate and the adhesive layer, in other words, to enhance the anchoring of the adhesive layer to the substrate. Alternatively, the substrate can be one on which the aforementioned surface treatments to improve anchoring are not applied. When forming a primer layer, there are no particular limitations on the primer used in its formation, and it can be appropriately selected from known primers. There are no particular limitations on the thickness of the primer layer; for example, it can be greater than 0.01 μm, typically 0.1 μm or more is appropriate, and from the viewpoint of improving effectiveness, it can be 0.2 μm or more. Furthermore, the thickness of the primer layer is preferably less than 1.0 μm, less than 0.7 μm, and less than 0.5 μm. Generally, primers are highly dependent on fossil resources. Therefore, from the perspective of reducing the biomass content of the adhesive sheet (described later), it is advantageous to keep the thickness of the primer layer relatively small.

[0180] In the case of a single-sided adhesive sheet with an adhesive layer on one side of the substrate, a release agent (back side treatment agent) can be used to perform a release treatment on the surface of the substrate where the adhesive layer does not form (the back side). There are no particular limitations on the back side treatment agent that can be used in the formation of the back side treatment layer; silicone-based back side treatment agents, fluorinated back side treatment agents, long-chain alkyl-based back side treatment agents, and other known or conventional treatment agents can be used, depending on the purpose and application. One back side treatment agent can be used alone or in combination of two or more.

[0181] Various additives, such as fillers (inorganic fillers, organic fillers, etc.), anti-aging agents, antioxidants, UV absorbers, antistatic agents, lubricants, plasticizers, and colorants (pigments, dyes, etc.), can be added to the substrate (e.g., resin film substrate) as needed. The proportion of each additive is typically about 30% by weight or less (e.g., about 20% by weight or less, typically about 10% by weight or less). For example, in the case where the substrate contains pigments (e.g., white pigments), a content of about 0.1% to about 10% by weight (e.g., about 1% to about 8% by weight, typically about 1% to about 5% by weight) is appropriate.

[0182] There are no particular limitations on the thickness of the substrate, and it can be appropriately selected according to the purpose, typically ranging from about 1 μm to about 500 μm. From the viewpoint of substrate processability, the thickness of the substrate can be, for example, 1.5 μm or more, 2 μm or more, 3 μm or more, 4 μm or more, or 4.5 μm or more. Furthermore, from the viewpoint of thinning the adhesive sheet, in some cases, the thickness of the substrate can be, for example, less than 150 μm, less than 100 μm, less than 50 μm, less than 25 μm, less than 20 μm, less than 10 μm, less than 7 μm, less than 5 μm, or less than 4 μm.

[0183] <Adhesive Sheet>

[0184] The thickness (total thickness) of the adhesive sheet disclosed herein (including an adhesive layer, and in the case of an adhesive sheet with a substrate, also including a substrate but excluding a release liner) is not particularly limited, and can, for example, be in the range of about 2 μm to about 1000 μm. In some embodiments, considering adhesive properties, the thickness of the adhesive sheet is preferably about 5 μm to about 500 μm (e.g., about 10 μm to about 300 μm, typically about 15 μm to about 200 μm). Alternatively, in embodiments where thinness is emphasized, the thickness of the adhesive sheet can be less than 100 μm (e.g., 5 μm to 100 μm), less than 70 μm (e.g., 5 μm to 70 μm), less than 45 μm (e.g., 5 μm to 45 μm), or less than 30 μm (e.g., 5 μm to 30 μm).

[0185] The adhesive sheet disclosed herein preferably contains approximately 30% or more (e.g., more than 30%) of its total carbon, which is derived from biomass. That is, the biomass content of the adhesive sheet is preferably 30% or more. By using an adhesive sheet with such a high biomass content, the amount of fossil-based materials used can be reduced. From this perspective, it can be said that the higher the biomass content of the adhesive sheet, the more satisfactory it is. The biomass content of the adhesive sheet is preferably 40% or more, but can be 50% or more, 60% or more, 70% or more, or 75% or more. While the upper limit of the biomass content is defined as 100%, setting all materials constituting the adhesive sheet to be derived from plants can result in low efficiency in terms of productivity and performance; therefore, the biomass content of the adhesive sheet can be less than 100%. From the viewpoint of easily obtaining performance (e.g., shear adhesive strength) suitable for use in portable electronic devices, in some cases, the biomass content of the adhesive sheet can be, for example, 90% or less; where adhesive performance is more important, the biomass content of the adhesive sheet can be 80% or less, or 70% or less.

[0186] It should be noted that in a substrate-free adhesive sheet consisting of an adhesive layer, the biomass ratio of the adhesive layer is consistent with the overall biomass ratio of the adhesive sheet.

[0187] The adhesive sheet disclosed herein preferably exhibits a strength greater than 100 N / 100 mm. 2 The shear adhesive strength exhibits a high degree of resistance to dynamic loads (i.e., shear forces) that would cause the adhesive interface to deviate, thus providing excellent retention of the bonded material. For example, it can effectively prevent peeling when securing components within portable electronic devices. From the viewpoint of achieving higher adhesive reliability, the shear adhesive strength of the adhesive sheet is preferably 180 N / 100 mm. 2 The above is preferred, with 220N / 100mm being even better. 2 The above is further optimized to 250N / 100mm. 2 The above is particularly preferred, with 280N / 100mm. 2 Above (e.g., 320N / 100mm) 2 (Above). There is no particular upper limit to the shear adhesive strength mentioned above; generally, a higher value is more desirable. However, considering other properties (such as holding power and other adhesive properties, and optical properties such as light transmittance if necessary), in some cases, the shear adhesive strength mentioned above can be, for example, 700 N / 100 mm. 2 The following can also be 500N / 100mm 2 The shear adhesive force described above can be measured using the method described in the examples described later.

[0188] Furthermore, the adhesive sheet disclosed herein exhibits a satisfactory level of resilience (i.e., no peeling) in a resilience test measured using a 125 μm thick PET film in the embodiments described later. The aforementioned resilient adhesive sheet demonstrates durability against bending and exhibits adhesive reliability without bulging or peeling, even when used in a manner where it is adhered to curved surfaces such as three-dimensional shapes.

[0189] For some types of adhesive sheets, the 180-degree peel strength (adhesion to SUS) to stainless steel sheets is preferably 10 N / 20 mm or more. Adhesive sheets exhibiting the above characteristics bond firmly to the substrate and are therefore typically preferred for use in a manner where no further peeling is intended. From the viewpoint of achieving a more reliable bond, the above-mentioned adhesion strength can be, for example, 11 N / 20 mm or more, preferably 12 N / 20 mm or more, 13 N / 20 mm or more, 14 N / 20 mm or more, or 15 N / 20 mm or more. There is no particular upper limit to the above-mentioned adhesion strength; in some cases, the adhesion strength can be, for example, 50 N / 20 mm or less, 30 N / 20 mm or less, or 25 N / 20 mm or less. The above-mentioned adhesion strength to SUS can be specifically measured by the methods described in the examples described later.

[0190] <Applications>

[0191] The adhesive sheet disclosed herein has no particular limitation in its application and can be used for a variety of purposes without restriction. For example, the adhesive sheet can be used to adhere to components constituting electronic devices, for purposes such as fixing, joining, or reinforcing the components. The adhesive sheet disclosed herein is preferably used, for example, in the form of a double-sided adhesive sheet for fixing or joining components. In this application, the adhesive sheet has good shear adhesion, which is particularly useful in preventing peeling. The aforementioned double-sided adhesive sheet can be substrate-free or substrate-containing. From the viewpoint of thinness, in some embodiments, substrate-free double-sided adhesive sheets or substrate-containing double-sided adhesive sheets using a thin substrate are preferred. As the aforementioned thin substrate, a substrate with a thickness of 10 μm or less (e.g., less than 5 μm) is preferred.

[0192] The adhesive sheet disclosed herein is suitable for applications such as component fixing in portable electronic devices. Based on high shear strength, the adhesive sheet exhibits high adhesive reliability, making it suitable for applications requiring high performance in portable electronic devices. Since the bonding area is limited in portable electronic devices, the use of adhesive sheets with high shear strength is particularly meaningful. Non-limiting examples of the aforementioned portable electronic devices include: mobile phones, smartphones, tablet PCs, laptop PCs, various wearable devices (e.g., wrist-worn types like watches, modular types worn on the body with clips or straps, including eyeglasses (monocular, binocular, and helmet types), clothing types worn as accessories on shirts, socks, hats, etc., and ear-worn types like headphones), digital cameras, digital camcorders, audio equipment (portable music players, voice recorders, etc.), calculators (desktop calculators, etc.), portable gaming devices, electronic dictionaries, electronic notebooks, e-books, in-vehicle information devices, portable radios, portable televisions, portable printers, portable scanners, portable modems, etc. The adhesive sheet disclosed herein, for example, in a portable electronic device with a pressure sensor, can preferably be used to secure the pressure sensor to other components. In some preferred embodiments, the adhesive sheet can be used in electronic devices (typically portable electronic devices) that have the function of specifying an absolute position on a panel (typically a touch panel) corresponding to the screen by means of a device for indicating the position on the screen (typically a pen-type or mouse-type device) and a device for detecting the position, to secure the pressure sensor to other components. It should be noted that in this specification, "portable" is not adequately interpreted as merely being able to carry; it essentially refers to a level of portability that is relatively easy for a person (standard adult) to move.

[0193] In addition, the adhesive sheet disclosed herein has good resilience, and therefore, based on this resilience, it can exhibit excellent adhesive reliability even when bent. It is preferably used to adhere to the curved surface of portable electronic devices with curved shapes such as three-dimensional shapes (e.g., portable electronic devices with displays having curved shapes).

[0194] In addition, as mentioned above, portable electronic devices may contain heat-generating components such as batteries, and therefore, when exposed to temperatures above 40°C, it is meaningful to use adhesive sheets with excellent high-temperature retention in the preferred manner disclosed herein, so as to obtain adhesive reliability without bulging or peeling even under the aforementioned high-temperature conditions.

[0195] There are no particular limitations on the materials (adhesive materials) used for bonding the adhesive sheet disclosed herein. Examples include: metallic materials such as copper, iron, aluminum, and stainless steel; various resin materials (typically plastic materials); inorganic materials such as glass; etc. Examples of the aforementioned resin materials include: polyimide resins, acrylic resins, polyether nitrile resins, polyether sulfone resins, polyester resins (PET resins, polyethylene naphthalate resins, etc.), polyvinyl chloride resins, polyphenylene sulfide resins, polyether ether ketone resins, polyamide resins (so-called aromatic polyamide resins, etc.), polyarylate resins, polycarbonate resins, liquid crystal polymers, etc. The adhesive sheet disclosed herein is preferably used for bonding the aforementioned metallic materials, polyester resins such as PET, polyimide resins, aromatic polyamide resins, polyphenylene sulfide resins, polycarbonate resins, etc. These materials can be used to construct components for products such as portable electronic devices. The adhesive sheet disclosed herein can be used to bond components made of the aforementioned materials.

[0196] Figure 4 This is an example illustrating a portable electronic device (smartphone) using the adhesive sheet disclosed herein. For example... Figure 4 As shown, a battery (heating element) 540 is built into the housing 520 of the portable electronic device 500. Furthermore, the portable electronic device 500 is configured to include an adhesive sheet 550. In this configuration, the adhesive sheet 550 has the form of a double-sided adhesive sheet (double-sided adhesive sheet) for fixing the components constituting the portable electronic device 500. It should be noted that the portable electronic device 500 includes a touch panel 570 that functions as both a display and an input unit. The adhesive sheet disclosed herein is preferably used as a component (component joining means) of the aforementioned portable electronic device.

[0197] The matters disclosed in this specification include the following.

[0198] [1] A portable electronic device, the portable electronic device having: a housing, and a touch panel that functions as both a display and an input unit, wherein...

[0199] A heating element (such as a battery) is built into the inside of the housing.

[0200] In the majority of the components constituting the portable electronic device, at least the first component and the second component are joined by an adhesive sheet.

[0201] The adhesive sheet has an adhesive layer containing a polyester polymer, wherein more than 50% of the carbon constituents in the polyester polymer are derived from biomass.

[0202] The adhesive layer also includes a tackifying resin and a crosslinking agent.

[0203] The polyester polymer contains aromatic rings, the tackifying resin also contains aromatic rings, and the crosslinking agent does not contain aromatic rings.

[0204] [2] According to the portable electronic device described in [1] above, the weight-average molecular weight of the polyester polymer is 30,000 or more.

[0205] [3] The portable electronic device according to [1] or [2] above, wherein the weight-average molecular weight of the polyester polymer is greater than 100,000.

[0206] [4] The portable electronic device according to any one of [1] to [3] above, wherein the glass transition temperature of the polyester polymer is below 0°C.

[0207] [5] The portable electronic device according to any one of [1] to [4] above, wherein the aromatic ring ratio of the tackifying resin is 20% by weight or more.

[0208] [6] The portable electronic device according to any one of [1] to [5] above, wherein the tackifying resin comprises a terpene phenol resin.

[0209] [7] The portable electronic device according to any one of [1] to [6] above, wherein the adhesive layer comprises an isocyanate crosslinking agent as the crosslinking agent.

[0210] [8] The portable electronic device according to any one of [1] to [7] above, wherein the adhesive layer comprises an aliphatic isocyanate compound as the crosslinking agent.

[0211] [9] The portable electronic device according to any one of [1] to [8] above, wherein the content of the crosslinking agent in the adhesive layer is 5 parts by weight or less relative to 100 parts by weight of the polyester polymer.

[0212]

[10] The portable electronic device according to any one of [1] to [9] above, wherein the adhesive layer further comprises a crosslinking catalyst that does not contain a tin-containing compound.

[0213]

[11] An adhesive composition comprising a polyester polymer, wherein more than 50% of the constitutive carbon in the polyester polymer is derived from biomass, wherein,

[0214] The adhesive composition further comprises a tackifying resin and a crosslinking agent.

[0215] The polyester polymer contains aromatic rings, the tackifying resin also contains aromatic rings, and the crosslinking agent does not contain aromatic rings.

[0216]

[12] According to the adhesive composition described in

[11] above, wherein the weight-average molecular weight of the polyester polymer is 30,000 or more.

[0217]

[13] The adhesive composition according to

[11] or

[12] above, wherein the weight-average molecular weight of the polyester polymer is greater than 60,000.

[0218]

[14] The adhesive composition according to any one of

[11] to

[13] above, wherein the weight-average molecular weight of the polyester polymer is greater than 100,000.

[0219]

[15] The adhesive composition according to any one of

[11] to

[14] above, wherein the glass transition temperature of the polyester polymer is below 0°C.

[0220]

[16] The adhesive composition according to any one of

[11] to

[15] above, wherein the aromatic ring ratio of the tackifying resin is 20% by weight or more.

[0221]

[17] The adhesive composition according to any one of

[11] to

[16] above, wherein the tackifying resin comprises a terpene phenol resin.

[0222]

[18] An adhesive composition according to any one of

[11] to

[17] above, wherein the adhesive composition comprises an isocyanate crosslinking agent as the crosslinking agent.

[0223]

[19] An adhesive composition according to any one of

[11] to

[18] above, wherein the adhesive composition comprises an aliphatic isocyanate compound as the crosslinking agent.

[0224]

[20] The adhesive composition according to any one of

[11] to

[19] above, wherein the content of the crosslinking agent is 5 parts by weight or less relative to 100 parts by weight of the polyester polymer.

[0225]

[21] The adhesive composition according to any one of

[11] to

[20] above, wherein the adhesive composition further comprises a crosslinking catalyst that does not contain a tin-containing compound.

[0226]

[22] The adhesive composition according to any one of

[11] to

[21] above, wherein the adhesive composition comprises a bifunctional crosslinking agent and a trifunctional or higher crosslinking agent as crosslinking agents.

[0227]

[31] An adhesive sheet having an adhesive layer comprising a polyester polymer, wherein more than 50% of the constitutive carbon in the polyester polymer is derived from biomass, wherein,

[0228] The adhesive layer also includes a tackifying resin and a crosslinking agent.

[0229] The polyester polymer contains aromatic rings, the tackifying resin also contains aromatic rings, and the crosslinking agent does not contain aromatic rings.

[0230]

[32] According to the adhesive sheet described in

[31] above, the weight-average molecular weight of the polyester polymer is 30,000 or more.

[0231]

[33] The adhesive sheet according to

[31] or

[32] above, wherein the weight-average molecular weight of the polyester polymer is greater than 60,000.

[0232]

[34] The adhesive sheet according to any one of

[31] to

[33] above, wherein the weight-average molecular weight of the polyester polymer is greater than 100,000.

[0233]

[35] The adhesive sheet according to any one of

[31] to

[34] above, wherein the glass transition temperature of the polyester polymer is below 0°C.

[0234]

[36] The adhesive sheet according to any one of

[31] to

[35] above, wherein the aromatic ring ratio of the tackifying resin is 20% by weight or more.

[0235]

[37] The adhesive sheet according to any one of

[31] to

[36] above, wherein the tackifying resin comprises a terpene phenol resin.

[0236]

[38] The adhesive sheet according to any one of

[31] to

[37] above, wherein the adhesive layer comprises an isocyanate crosslinking agent as the crosslinking agent.

[0237]

[39] The adhesive sheet according to any one of

[31] to

[37] above, wherein the adhesive layer comprises an aliphatic isocyanate compound as the crosslinking agent.

[0238]

[40] The adhesive sheet according to any one of

[31] to

[39] above, wherein the content of the crosslinking agent in the adhesive layer is 5 parts by weight or less relative to 100 parts by weight of the polyester polymer.

[0239]

[41] The adhesive sheet according to any one of

[31] to

[40] above, wherein the adhesive layer further comprises a crosslinking catalyst that does not contain a tin-containing compound.

[0240]

[42] The adhesive sheet according to any one of

[31] to

[41] above, wherein the adhesive layer comprises a bifunctional crosslinking agent and a trifunctional or higher crosslinking agent as a crosslinking agent.

[0241]

[43] The adhesive sheet according to any one of

[31] to

[42] above, wherein the shear adhesive force of the adhesive sheet to the stainless steel plate is greater than 100 N / 100 mm. 2 .

[0242]

[44] The adhesive sheet according to any one of

[31] to

[43] above, wherein the adhesive sheet has a 180-degree peel strength of 10 N / 20 mm or more against the stainless steel sheet.

[0243]

[51] An adhesive sheet according to any one of

[31] to

[44] above, wherein the adhesive sheet is used in a portable electronic device.

[0244]

[52] A portable electronic device, wherein the portable electronic device comprises the adhesive sheet described in any one of

[31] to

[44] above.

[0245] Example

[0246] The following describes some embodiments of the present invention, but it is not intended to limit the present invention to the contents shown in these embodiments. It should be noted that, unless otherwise specified, "parts" and "%" in the following description are based on weight.

[0247] <Evaluation Methods>

[0248] [Shear Adhesive Strength]

[0249] The adhesive sheet (double-sided adhesive sheet) was cut into 10mm × 10mm dimensions to prepare the test samples. At 23°C and 50% RH, the adhesive surfaces of the test samples were overlapped onto the surfaces of two stainless steel plates (SUS304BA plates), and pressed together once by a 2kg roller. After being placed in the same environment for 2 days, the shear adhesive force [N / 100mm] was measured using a tensile testing machine at a tensile speed of 10mm / min and a peel angle of 0 degrees. 2 If the shear adhesive strength is greater than 100 N / 100 mm. 2 If the adhesive strength is high, it is evaluated as having high shear adhesive strength. In the case of single-sided adhesive sheets (single-sided adhesive sheets), the non-adhesive side of the sheet is fixed to the stainless steel plate with adhesive or the like, and the measurement is performed in the same manner as described above. As a tensile testing machine, a universal tensile-compression testing machine (product name "TG-1kN", manufactured by Minebea Corporation) can be used.

[0250] [Rebound Resistance Test]

[0251] like Figure 5 As shown in (a), a polycarbonate (PC) sheet 50 with a length of 30 mm, a width of 10 mm, and a thickness of 2 mm and a PET film 60 with a length of 100 mm, a width of 10 mm, and a thickness of 125 μm are prepared. The PC sheet 50 and the PET film 60 are overlapped with one end aligned along their length, and the remaining part of the PET film 60 protrudes from the other end of the PC sheet 50. The PC sheet 50 and the PET film 60 are then fixed together. The above fixation is achieved using commercially available double-sided adhesive tape (manufactured by Nitto Denko Corporation, "No. 5000NS").

[0252] Each adhesive sheet, with its two adhesive surfaces protected by two release liner pads, is cut into 10mm x 10mm dimensions, thus preparing an adhesive sheet sample 70. With the surface opposite to the fixing surface of the PET film on the PC board 50 positioned on the upper side, one release liner is peeled off from the adhesive sheet sample 70, and the adhesive sheet sample 70 is adhered and fixed to the upper surface of the PC board 50 with the other end of the PC board 50 aligned with one side of the adhesive sheet sample 70. This fixing is performed by reciprocating once with a 2kg roller on the upper surface of the adhesive sheet sample 70 protected by the other release liner.

[0253] Next, at 23°C and 50% RH, another release liner of the adhesive sheet sample 70, which was adhered to the PC board 50, was peeled off, as shown below. Figure 5(b) shows that the portion (70 mm in length) of the PET film 60 protruding from the PC board 50 and fixed to the PC board 50 is folded back towards the PC board 50, so that the adhesive sheet sample 70 is aligned with the other end (free end) of the PET film 60. A 0.1 kg roller is then passed over the PET film 60 once, thereby fixing the other end of the bent PET film 60 to the upper surface of the PC board 50 via the adhesive sheet sample 70. The peeling of the PET film 60 from the adhesive sheet sample 70 was observed for 24 hours at 60°C, 95% RH, and room temperature (23°C), respectively. The adhesive holding force of the adhesive sheet sample 70 relative to the thickness direction of the adhesive sheet, based on the elastic rebound of the bent PET film 60, was evaluated as the resilience.

[0254] The adhesion state of the adhesive sheet sample 70 to the PET film 60 after 24 hours at 60℃, 95%RH, and room temperature is judged as "◎"; the adhesion state of the adhesive sheet sample 70 to the PET film 60 after 24 hours at room temperature is judged as "〇"; and the adhesion state within 24 hours at 60℃, 95%RH, and room temperature is judged as "〇". Figure 5 (c) The peeling condition of the PET film 60 shown is judged as "×". A result of ◎ or 〇 in the rebound test is evaluated as having good rebound resistance (i.e., qualified), and a result of × is evaluated as having insufficient rebound resistance (i.e., unqualified).

[0255] [Adhesion to SUS]

[0256] The adhesive sheet was cut into pieces 20 mm wide and 150 mm long to prepare the test sample. Under conditions of 23°C and 50% RH, the adhesive surface of the test sample was exposed, and a 2 kg rubber roller was applied once to press the adhesive surface of the test sample onto a stainless steel plate (SUS304BA plate) used as the substrate. It was then placed at 23°C and 50% RH for 30 minutes, and then, under the same conditions, the peel strength (adhesive force against SUS) [N / 20 mm] was measured using a tensile testing machine according to JIS Z0237:2000, at a peel angle of 180 degrees and a tensile speed of 300 mm / min. A universal tensile-compression testing machine (device name "Tensile-Compression Testing Machine, TCM-1kNB", manufactured by Minebea Corporation) can be used as the tensile testing machine.

[0257] It should be noted that when measuring the adhesion to SUS, depending on the needs (e.g., in the case of a double-sided adhesive sheet without a substrate, or in the case of an adhesive sheet with a substrate that is easily deformable), an appropriate substrate material can be attached to the adhesive sheet to be tested for reinforcement. For example, a PET film with a thickness of approximately 50 μm can be used as the substrate material; this substrate material was used in the examples.

[0258] <Synthesis example>

[0259] (Synthesis example 1)

[0260] A separable four-necked flask equipped with a stirrer, thermometer, nitrogen tube, and water separator was used to add 100 g of ethylene glycol (manufactured by Tokyo Chemical Industry Co., Ltd., molecular weight 62), 700 g of dimer acid (product name "Pripol 1009", manufactured by Croda Co., Ltd., molecular weight 567), 63 g of terephthalic acid (manufactured by Tokyo Chemical Industry Co., Ltd., molecular weight 166), 0.46 g of di-n-butyltin oxide (manufactured by Kishida Chemical Co., Ltd., molecular weight 249) as a polymerization catalyst, and 40 g of xylene as a solvent for removing reaction water. The mixture was stirred under a nitrogen atmosphere and heated to 180°C, which was then maintained. Soon, reaction water was observed to flow out and separate, indicating the start of the reaction. The reaction continued for approximately 24 hours, yielding a polyester polymer (A1) with a biomass content of 81%. This polyester polymer (A1) had a weight-average molecular weight (Mw) of 100,000 and a glass transition temperature (Tg) of -33°C.

[0261] (Synthesis example 2)

[0262] A separable four-necked flask equipped with a stirrer, thermometer, nitrogen tube, and water separator was used to add 100 g of ethylene glycol (manufactured by Tokyo Chemical Industry Co., Ltd., molecular weight 62), 915 g of dimer acid (product name "Pripol 1009", manufactured by Croda Co., Ltd., molecular weight 567), 0.46 g of di-n-butyltin oxide (manufactured by Kishida Chemical Co., Ltd., molecular weight 249) as a polymerization catalyst, and 40 g of xylene as a solvent for removing reaction water. The mixture was stirred under a nitrogen atmosphere and heated to 180°C, which was then maintained. Soon, reaction water was observed to flow out and separate, indicating the start of the reaction. The reaction continued for approximately 24 hours, yielding a polyester polymer (A2) with a biomass content of 89%. This polyester polymer (A2) has a molecular weight of 100,000 and a glass transition temperature (Tg) of -36°C.

[0263] (Synthesis example 3)

[0264] Except that the reaction time in Synthesis Example 1 was changed to approximately 36 hours, a polyester polymer (A3) with a higher molecular weight than that of polyester polymer (A1) was obtained in the same manner as in Synthesis Example 1. The monomer composition of this polyester polymer (A3) is the same as that of polyester polymer (A1), with a molecular weight of 130,000.

[0265] <Example 1>

[0266] A terpene phenol resin (trade name "YSPOLYSTER S145", manufactured by Yasuhara Chemical Co., Ltd., with a phenol ratio of 22%, sometimes referred to as "S145" below) was added to 100 parts of a polyester polymer (A1), 40 parts of isocyanurate of hexamethylene diisocyanate (trade name "Coronate HX", manufactured by Tosoh Co., Ltd., without aromatic ring, hereinafter also referred to as "trifunctional crosslinking agent"), 3 parts of organozirconium compound (trade name "ORGATIX ZC-162", manufactured by Matsumoto Fine Chemicals Co., Ltd.) as crosslinking catalyst, 0.5 parts of carbodiimide-containing compound (trade name "CARBODILITE V-03", manufactured by Nisshinbo Chemical Co., Ltd.) as hydrolysis resistant agent, and ethyl acetate was added to prepare an adhesive composition (adhesive solution). The adhesive solution was applied to the release-treated surface of a polyethylene terephthalate (PET) film (trade name "Diafoil MRF#38", manufactured by Mitsubishi Chemical Corporation) with a dried thickness of 20 μm, and dried at 120°C for 3 minutes to obtain an adhesive layer. Then, the adhesive layer was bonded to the release-treated surface of the PET film (trade name "Diafoil MRE#38", manufactured by Mitsubishi Chemical Corporation), and further placed at 50°C for 3 days to obtain the substrate-free adhesive sheet of this example.

[0267] <Example 2>

[0268] Except that 0.01 parts of an organotin compound (trade name "Dibutyltin dilaurate (IV)", manufactured by Fujifilm and Koujun Pharmaceutical Co., Ltd.) were used instead of an organozirconium compound as a crosslinking catalyst, the adhesive composition of this example was prepared in the same manner as in Example 1. In addition to using the adhesive composition, the substrate-free adhesive sheet of this example was obtained in the same manner as in Example 1.

[0269] <Example 3>

[0270] The amount of crosslinking agent was changed to 4 parts per 100 parts of the polyester polymer (A1), and 0.13 parts of an organoaluminum compound (trade name "NACEM aluminum" (aluminum acetylacetonate), manufactured by Nippon Chemical Industries, Ltd.) was used instead of the organozirconium compound as the crosslinking catalyst. Otherwise, the adhesive composition of this example was prepared in the same manner as in Example 1, and the substrate-free adhesive sheet of this example was obtained in the same manner as in Example 1, except that a substrate-free adhesive sheet was obtained using this adhesive composition.

[0271] <Example 4>

[0272] To 100 parts of a polyester polymer (A3), 40 parts of a terpene phenolic resin (trade name "YSPOLYSTER G150", manufactured by Yasuhara Chemical Co., Ltd., with a phenol content of 32%, sometimes referred to as "G150" below) as a tackifying resin, 2 parts of crosslinking agent A (trade name "Coronate HX", manufactured by Tosoh Co., Ltd.), 0.03 parts of an organozirconium compound (trade name "ORGATIX ZC-162", manufactured by Matsumoto Fine Chemicals Co., Ltd.) as a crosslinking catalyst, and 0.5 parts of a carbodiimide-containing compound (trade name "CARBODILITE V-03", manufactured by Nisshinbo Chemical Co., Ltd.) as a hydrolysis resistant agent were added, along with ethyl acetate, thereby preparing an adhesive composition (adhesive solution). In addition to using the obtained adhesive composition, a substrate-free adhesive sheet (thickness 20 μm) of this example was obtained in the same manner as in Example 1.

[0273] <Example 5>

[0274] Except for the use of 40 parts of terpene phenol resin (trade name "YSPOLYSTER S145", manufactured by Yasuhara Chemical Co., Ltd., phenol ratio 22%) as tackifying resin, 3 parts of crosslinking agent A (trade name "Coronate HX", manufactured by Tosoh Co., Ltd.), and 0.01 parts of organotin compound (trade name "dibutyltin dilaurate (IV)", manufactured by Fujifilm and Koko Pure Chemical Co., Ltd.) as crosslinking catalyst in 100 parts of polyester polymer (A3), the adhesive composition of this example was prepared in the same manner as in Example 4. Except for the use of the adhesive composition, the substrate-free adhesive sheet of this example was obtained in the same manner as in Example 4.

[0275] <Example 6>

[0276] To 100 parts of a polyester polymer (A1), 40 parts of a terpene phenolic resin (trade name "YSPOLYSTER G150", manufactured by Yasuhara Chemical Co., Ltd., phenol ratio 32%), 2 parts of crosslinking agent A (trade name "Coronate HX", manufactured by Tosoh Co., Ltd.), 2 parts of a bifunctional crosslinking agent (trade name "DURANATE D101", manufactured by Asahi Kasei Co., Ltd., aromatic ring-free), 0.03 parts of an organozirconium compound (trade name "ORGATIX ZC-162", manufactured by Matsumoto Fine Chemicals Co., Ltd.), and 0.5 parts of a carbodiimide-containing compound (trade name "CARBODILITE V-03", manufactured by Nisshinbo Chemical Co., Ltd.), a hydrolysis-resistant agent, were added, along with ethyl acetate, thereby preparing an adhesive composition (adhesive solution). In addition to using the obtained adhesive composition, a substrate-free adhesive sheet (thickness 20 μm) of this example was obtained in the same manner as in Example 1.

[0277] <Example 7>

[0278] Polyester polymer (A2) was used instead of polyester polymer (A1), and the amount of crosslinking agent used was changed to 5 parts per 100 parts of polyester polymer (A2). Otherwise, the adhesive composition of this example was prepared in the same manner as in Example 2, and the substrate-free adhesive sheet of this example was obtained in the same manner as in Example 2, except that the adhesive composition was used.

[0279] <Example 8>

[0280] As the tackifying resin, 20 parts of hydrogenated rosin glycerol ester (trade name "HARITACK SE10", manufactured by Halima Chemical Co., Ltd.) were used instead of 40 parts of terpene phenol resin S145. As the crosslinking agent, 2 parts of crosslinking agent B containing aromatic rings (trade name "Coronate L", 75% ethyl acetate solution of trimethylolpropane / toluene diisocyanate trimer adduct, manufactured by Tosoh Co., Ltd.) were used relative to 100 parts of the polyester polymer (A1). Otherwise, the adhesive composition of this example was prepared in the same manner as in Example 1, and the substrate-free adhesive sheet of this example was obtained in the same manner as in Example 1, except that the obtained adhesive composition was used.

[0281] For the adhesive sheets obtained in each example, the shear adhesive force and the SUS adhesive force were measured using the methods described above. Additionally, a rebound resistance test was performed on Examples 2, 4 through 8. The results are shown in Table 1.

[0282]

[0283] As shown in Table 1, in adhesives containing polyester polymers with a biomass content of 50% or more, the adhesives of Examples 1 to 6, in which the polyester polymer and tackifying resin contain aromatic rings and the crosslinking agent does not contain aromatic rings, have an N / 100 mm ratio greater than 100 N / 100 mm. 2 High shear adhesive strength was achieved. Furthermore, the rebound resistance test results for Examples 2, 4-6 were satisfactory, with the rebound resistance test results for Examples 4-6 being particularly excellent. On the other hand, high shear adhesive strength could not be obtained in Example 7, which used a polyester polymer without aromatic rings. High shear adhesive strength also could not be obtained in Example 8, which used a tackifying resin without aromatic rings and a crosslinking agent containing aromatic rings.

[0284] The results above show that high shear strength can be obtained by using an adhesive that contains polyester polymers, tackifying resins, and crosslinking agents in which more than 50% of the carbon composition is derived from biomass, and where the polyester polymers and tackifying resins contain aromatic rings and the crosslinking agents do not contain aromatic rings.

[0285] The specific examples of the present invention have been described in detail above, but they are merely illustrative and do not limit the scope of the claims. The technology described in the claims includes technical solutions obtained by various modifications and alterations to the specific examples described above.

[0286] Label Explanation

[0287] 1, 2, 3 Adhesive sheets

[0288] 10 Supporting substrate

[0289] 10A First Page

[0290] 10B Second side (back)

[0291] 21 Adhesive layer (first adhesive layer)

[0292] 21A Adhesive Surface (First Adhesive Surface)

[0293] 21B Second Adhesive Surface

[0294] 22 Adhesive layer (second adhesive layer)

[0295] 22A Adhesive Surface (Second Adhesive Surface)

[0296] 31, 32 Peeling off the gasket

[0297] 100, 200, 300 Adhesive sheets with release liner

Claims

1. An adhesive composition, wherein, The adhesive composition comprises a polyester polymer, wherein more than 50% of the carbon constituents in the polyester polymer are derived from biomass. The adhesive composition further comprises a tackifying resin and a crosslinking agent. The polyester polymer contains aromatic rings, the tackifying resin also contains aromatic rings, and the crosslinking agent does not contain aromatic rings. The weight-average molecular weight of the polyester polymer is greater than 60,000.

2. The adhesive composition according to claim 1, wherein, The weight-average molecular weight of the polyester polymer is greater than 100,000.

3. The adhesive composition according to claim 1 or 2, wherein, The aromatic ring ratio of the tackifying resin is 20% or more by weight.

4. The adhesive composition according to claim 1 or 2, wherein, The tackifying resin comprises a terpene phenol resin.

5. The adhesive composition according to claim 1 or 2, wherein, The adhesive composition contains an aliphatic isocyanate compound as the crosslinking agent.

6. An adhesive sheet having an adhesive layer comprising a polyester polymer, wherein more than 50% of the constituent carbon in the polyester polymer is derived from biomass, wherein, The adhesive layer also includes a tackifying resin and a crosslinking agent. The polyester polymer contains aromatic rings, the tackifying resin also contains aromatic rings, and the crosslinking agent does not contain aromatic rings. The weight-average molecular weight of the polyester polymer is greater than 60,000.

7. The adhesive sheet according to claim 6, wherein, The aromatic ring ratio of the tackifying resin is 20% by weight or more.

8. The adhesive sheet according to claim 6 or 7, wherein, The tackifying resin comprises a terpene phenol resin.

9. The adhesive sheet according to claim 6 or 7, wherein, The adhesive sheet contains an aliphatic isocyanate compound as the crosslinking agent.

10. The adhesive sheet according to claim 6 or 7, wherein, The adhesive sheet has a shear adhesion force greater than 100 N / 100 mm to the stainless steel plate. 2 .

11. The adhesive sheet according to claim 6 or 7, wherein, The adhesive sheet is used in portable electronic devices.

12. A portable electronic device, wherein, The portable electronic device includes the adhesive sheet according to any one of claims 6 to 11.

Citation Information

Patent Citations

  • JP1974014132A

  • Adhesive sheet

    JP2020079372A

  • Washing and drying facility for glass appliance for medical experiment

    JP2021030200A

  • Renewable compositions

    WO2009079213A2

  • Adhesive composition, adhesive layer, adhesive tape, and double-sided adhesive tape

    CN105829482A